Adhesive sheet and laminate

By using adhesive sheets with specific laminated structures, the problems of reduced luminous efficiency and increased power consumption caused by black packaging materials are solved, and high-efficiency light extraction and reflection are achieved, improving display effect and energy efficiency.

CN119895005APending Publication Date: 2025-04-25NITTO DENKO CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202380069724.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-30
Filing Date
2023-09-13
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

When the LED chip is covered with a black packaging material, there are problems such as reducing luminous efficiency, darkening of image, and increasing power consumption, and it is difficult to take into account the functions of preventing metal wiring reflection and RGB color mixing.

Method used

An adhesive sheet having a specific laminated structure is used, wherein the visible light transmittance, energy storage modulus and thickness of the first and second adhesive layers are within a predetermined range to form a laminated body with high efficiency light extraction and low reflection.

Benefits of technology

It realizes efficient light extraction and excellent reflection reduction functions, improves luminous efficiency and contrast, and reduces power consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119895005A_ABST
    Figure CN119895005A_ABST
Patent Text Reader

Abstract

The present invention relates to an adhesive sheet in which the adhesive sheet has a laminated structure in which a first adhesive layer, a second adhesive layer, and a substrate are laminated in this order, the visible light transmittance T1 of the first adhesive layer and the visible light transmittance T2 of the second adhesive layer satisfying T1lt; the thickness of the second adhesive layer is less than 100 [mu] m, and the storage modulus G1'of the first adhesive layer at 90 DEG C and the storage modulus G2 'of the second adhesive layer at 90 DEG C satisfy G1'lt, G2'.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a pressure-sensitive adhesive sheet and a laminate. Background Art

[0002] In recent years, self-luminous display devices represented by mini / micro LED display devices (Mini / Micro Light Emitting Diode Display) have been proposed as next-generation display devices. As for mini / micro LED display devices, as a basic structure, a substrate in which a plurality of tiny LED light-emitting elements (LED chips) are densely arranged is used as a display panel, and the LED chips are encapsulated by an encapsulation material, and a protective member such as a resin film and a glass plate is laminated on the outermost layer.

[0003] There are many types of self-luminous display devices such as small / micro LED display devices, such as white backlight type, white light emitting color filter type, RGB type, etc., but in the white light emitting color filter type and RGB type, in order to prevent reflection of metal wiring or metal oxides such as ITO arranged on the substrate of the display panel, black packaging materials are sometimes used (for example, refer to Patent Documents 1 to 4). Among them, in the small / micro LED display device of the RGB type in which LED chips are arranged, the above-mentioned black packaging material can help prevent RGB color mixing and improve contrast.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2019-204905

[0007] Patent Document 2: Japanese Patent Application Publication No. 2017-203810

[0008] Patent Document 3: Japanese Patent Application No. 2018-523854

[0009] Patent Document 4: Japanese Patent Application Publication No. 2021-161263 Summary of the invention

[0010] Problems to be solved by the invention

[0011] When the black encapsulation material described in Patent Documents 1 to 3 is used, the upper part (image display side) of the light-emitting element such as the LED chip is covered by the black encapsulation material with reduced transmittance to visible light, so there is a problem of reduced luminous efficiency and darkened image. In order to cope with this situation, when the output power of the LED chip is increased to increase the luminous brightness, there is a problem of increased power consumption.

[0012] In addition, when the transmittance of the black encapsulation material to visible light is increased to improve the luminous efficiency, there is a trade-off relationship in preventing reflection of the above-described metal wiring or the like, and preventing color mixing of RGB or reduction of contrast. It is a difficult problem to have both of these functions.

[0013] In Patent Document 4, as an encapsulation material capable of solving the above problems, an optical laminate in which adhesive layers having different visible light transmittances are laminated is disclosed. However, depending on the size of the self-luminous display device, particularly the LED chip, there is room for research because the luminous efficiency in the micro-LED display device sometimes decreases.

[0014] The present invention has been made in view of the above circumstances, and provides an adhesive sheet having a high light extraction function and an excellent antireflection function, and a laminate using the adhesive sheet.

[0015] Means for Solving the Problems

[0016] The inventors of the present invention conducted in-depth research to solve the above problems. As a result, it was found that in an adhesive sheet having a laminated structure in which a first adhesive layer, a second adhesive layer, and a substrate are laminated in this order, by making the visible light transmittance, storage modulus of the first adhesive layer and the second adhesive layer, and the thickness of the second adhesive layer within a specified range, an adhesive sheet and a laminate having a high light extraction function and an excellent antireflection function can be obtained, and thus the present invention was completed.

[0017] That is, the present invention is as follows. [1]

[0019] An adhesive sheet, wherein the adhesive sheet has a laminated structure in which a first adhesive layer, a second adhesive layer, and a substrate are laminated in this order, the visible light transmittance T1 of the first adhesive layer and the visible light transmittance T2 of the second adhesive layer satisfy T1 < T2, the thickness of the second adhesive layer is less than 100 μm, and the storage modulus G1' of the first adhesive layer at 90°C and the storage modulus G2' of the second adhesive layer at 90°C satisfy G1' < G2'. [2]

[0021] The adhesive sheet according to [1], wherein G1' and G2' satisfy G1' / G2' < 0.3. [3]

[0023] The adhesive sheet according to [1], wherein at least one of the first adhesive layer and the second adhesive layer is an adhesive layer formed of an adhesive composition selected from a photocurable adhesive composition and a solvent-based adhesive composition. [4]

[0025] The adhesive sheet according to [1], wherein the first adhesive layer contains a colorant. [5]

[0027] The adhesive sheet according to [4], wherein the colorant contains carbon black. [6]

[0029] The adhesive sheet according to [1], wherein the thickness of the first adhesive layer is 5 μm to 10 μm. [7]

[0031] The adhesive sheet according to [1], wherein the thickness of the second adhesive layer is 10 μm to 99 μm. [8]

[0033] A laminate, wherein a substrate having a chip component and the adhesive sheet according to any one of [1] to [7] are laminated. [9]

[0035] A laminate, which is a laminate in which a display panel having a light-emitting element on a substrate, a first adhesive layer, a second adhesive layer, and a base material are laminated in this order, wherein the visible light transmittance T1 of the first adhesive layer and the visible light transmittance T2 of the second adhesive layer satisfy T1 < T2, and the thickness of the first adhesive layer in a portion of the substrate that does not have the light-emitting element is 2.5 times or more the thickness of the first adhesive layer in a portion of the substrate that has the light-emitting element.

[10]

[0037] The laminate according to [9], wherein the display panel is an LED panel having a micro LED chip on a substrate.

[0038] Advantages of the Invention

[0039] It is possible to provide an adhesive sheet having a high light extraction function and an excellent antireflection function, and a laminate using the adhesive sheet. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 It is an example of a schematic view (cross-sectional view) of the adhesive sheet of the embodiment of the present invention.

[0041] Figure 2 It is an example of a schematic view (cross-sectional view) of the laminate (micro LED display device) of the embodiment of the present invention. DETAILED DESCRIPTION OF THE INVENTION

[0042] Hereinafter, embodiments of the present invention will be described with reference to the drawings, but these are merely examples, and the present invention is not limited thereto.

[0043] [Adhesive Sheet]

[0044] The adhesive sheet according to an embodiment of the present invention has a laminated structure in which a first adhesive layer, a second adhesive layer, and a substrate are laminated in this order. The visible light transmittance T1 of the first adhesive layer and the visible light transmittance T2 of the second adhesive layer satisfy T1 < T2. The thickness of the second adhesive layer is less than 100 μm. The storage modulus G1' of the first adhesive layer at 90°C and the storage modulus G2' of the second adhesive layer at 90°C satisfy G1' < G2'.

[0045] The adhesive sheet according to an embodiment of the present invention can be used for the laminate described later.

[0046] Figure 1 is an example of a schematic view (cross-sectional view) of the adhesive sheet according to an embodiment of the present invention. As Figure 1 shown, the adhesive sheet 10 according to an embodiment of the present invention has a laminated structure in which a first adhesive layer 1, a second adhesive layer 2, and a substrate 3 are laminated in this order.

[0047] To explain the adhesive sheet, the configuration of the laminate according to an embodiment of the present invention will be described.

[0048] The laminate according to an embodiment of the present invention is a laminate in which a substrate having a chip component is laminated with the adhesive sheet according to an embodiment of the present invention. The laminate according to an embodiment of the present invention can be appropriately manufactured using the adhesive sheet according to an embodiment of the present invention.

[0049] For example, in the case of encapsulating a substrate having a fine chip component such as a self-luminous body, the substrate can be encapsulated by arranging and pressing the substrate having the chip component and the adhesive sheet according to an embodiment of the present invention such that the surface on the side of the first adhesive layer of the adhesive sheet faces the chip component.

[0050] Hereinafter, the case where a display panel having an LED chip on a substrate is used as an adherend of the adhesive sheet according to an embodiment of the present invention will be sometimes cited as an example for explanation, but the present invention is not limited thereto.

[0051] Figure 2 is an example of a schematic view (cross-sectional view) of the laminate (micro LED display device) according to an embodiment of the present invention. In Figure 2 the laminate (micro LED display device) 20 according to an embodiment of the present invention described later, a display panel in which a plurality of LED chips 7 are arranged on one side of a substrate 5, a first adhesive layer 1, a second adhesive layer 2, and a substrate 3 are laminated in this order.

[0052] In an embodiment of the present invention, a metal wiring layer 6 for sending a light emission control signal to each LED chip 7 can be laminated on the substrate 5 of the display panel. In Figure 2Among them, each LED chip 7 that emits light of each color of red (R), green (G), and blue (B) is alternately arranged on the substrate 5 of the display panel隔着金属布线层6. In the prior art, the metal wiring layer 6 is formed of a metal such as copper, and sometimes reflects the light emitted by each LED chip 7, thereby reducing the visual recognition of the image. In addition, there is a case where the light emitted by each LED chip 7 of each of the RGB colors is mixed, and the contrast is reduced.

[0053] In an embodiment of the present invention, each LED chip 7 arranged on the display panel is encapsulated without a gap by the first adhesive layer 1 and the second adhesive layer 2. That is, the adhesive sheet of the embodiment of the present invention can be an encapsulation material for each LED chip 7 through the laminated structure of the first adhesive layer 1 and the second adhesive layer 2.

[0054] [Visible light transmittance of the adhesive layer]

[0055] In the adhesive sheet 10 of the embodiment of the present invention, the visible light transmittance T1 of the first adhesive layer 1 and the visible light transmittance T2 of the second adhesive layer 2 satisfy T1 < T2. That is, the visible light transmittance of the first adhesive layer 1 is less than the visible light transmittance of the second adhesive layer 2.

[0056] The visible light transmittance T1 of the first adhesive layer 1 is not particularly limited. For example, it is 80% or less, and can be 70% or less, 60% or less, 50% or less, 40% or less, 30% or less, 20% or less, or 10% or less. By the visible light transmittance T1 of the first adhesive layer being 80% or less, it is easy to make the transmittance lower than the visible light transmittance T2 of the second adhesive layer. As described above, by encapsulating between the metal wiring of the laminate and the light-emitting element, reflection of the metal wiring, etc., and color mixing between the light-emitting elements can be prevented, and the contrast can be improved.

[0057] By making the visible light transmittance T1 of the first adhesive layer 1 within the above range, the adhesive sheet of the embodiment of the present invention can be used as a black matrix sheet described later.

[0058] The visible light transmittance T2 of the second adhesive layer is not particularly limited. For example, it is 85% to 100%, and can be 88% or more, 90% or more, or 92% or more. By the high transmittance of the second adhesive layer, for example, in the case where the adhesive sheet is used for encapsulating a light-emitting element, etc., the luminous efficiency is improved.

[0059] The visible light transmittance of each adhesive layer can be measured by the method described later.

[0060] [Thickness of the adhesive layer]

[0061] In an embodiment of the present invention, from the viewpoint of fully encapsulating the light-emitting element while preventing the first adhesive layer from remaining easily on the upper part (image display side) of the light-emitting element, the thickness of the first adhesive layer 1 can be adjusted to, for example, 0.1 to 2.0 times the height of the light-emitting element, preferably 0.2 to 1.5 times, and more preferably 0.3 to 1.2 times.

[0062] Specifically, the thickness of the first adhesive layer is, for example, about 0.5 μm to about 30 μm, preferably 2 μm to 20 μm, and more preferably 5 μm to 10 μm. Specifically, the thickness of the first adhesive layer may be greater than 0.5 μm, greater than 2 μm, or greater than 5 μm. The thickness of the first adhesive layer may be less than 30 μm, less than 20 μm, or less than 10 μm.

[0063] In an embodiment of the present invention, the thickness of the second adhesive layer 2 is less than 100 μm. Since the thickness of the second adhesive layer is less than 100 μm, when the light-emitting element (micro LED light-emitting element) arranged on the display panel is encapsulated using the adhesive sheet of the embodiment of the present invention, it is easily affected by the hardness of the substrate. In addition, the stress relaxation property of the second adhesive layer is reduced, so it is not easy to leave the first adhesive layer with a lower visible light transmittance on the upper part (image display side) of the light-emitting element. Therefore, the luminous efficiency of the light-emitting element can be improved.

[0064] Specifically, the thickness of the second adhesive layer is, for example, about 5 μm to about 99 μm, preferably 10 μm to 99 μm, more preferably 10 μm to 95 μm, further preferably 20 μm to 85 μm, and particularly preferably 25 μm to 75 μm. The thickness of the second adhesive layer may be 5 μm or more, 10 μm or more, 20 μm or more, or 25 μm or more. In addition, the thickness of the second adhesive layer may be 99 μm or less, 95 μm or less, 85 μm or less, 75 μm or less, or 50 μm or less.

[0065] The total thickness of the first adhesive layer 1 and the second adhesive layer 2 is not particularly limited, as long as it is appropriately set to be greater than the height of the light-emitting element in a manner that can fully encapsulate the light-emitting element arranged on the display panel described later. For example, the total thickness of the first adhesive layer 1 and the second adhesive layer 2 can be adjusted to 1.0 times to 13.0 times the height of the light-emitting element, preferably 1.3 times to 11.0 times, more preferably 1.6 times to 10.0 times, and further preferably 2.0 times to 9.0 times.

[0066] Specifically, the total thickness of the first adhesive layer 1 and the second adhesive layer 2 is, for example, about 5.0 μm to about 200 μm, and can be 5.0 μm or more, 10.0 μm or more, 15.0 μm or more, or 20.0 μm or more. Additionally, the total thickness of the first adhesive layer 1 and the second adhesive layer 2 can be, for example, 200 μm or less, 160 μm or less, 120 μm or less, or 90 μm or less.

[0067] The ratio of the thickness of the second adhesive layer to the thickness of the first adhesive layer (thickness of the second adhesive layer / thickness of the first adhesive layer) is not particularly limited. For example, (thickness of the second adhesive layer / thickness of the first adhesive layer) is, for example, about 0.1 to about 200.0, preferably 1.0 to 100.0, more preferably 2.0 to 50.0, and even more preferably 2.5 to 15.0.

[0068] [Storage modulus of the adhesive layer]

[0069] In the adhesive sheet 10 of the embodiment of the present invention, the storage modulus G1' of the first adhesive layer 1 at 90°C and the storage modulus G2' of the second adhesive layer 2 at 90°C satisfy G1' < G2'. That is, the storage modulus of the first adhesive layer 1 is less than the storage modulus of the second adhesive layer 2.

[0070] By G1' being less than G2', when using the adhesive sheet of the embodiment of the present invention to encapsulate, for example, light-emitting elements (micro-LED light-emitting elements) arranged on a display panel described later, the first adhesive layer 1 with a lower storage modulus is easily crushed by the second adhesive layer 2 with a higher storage modulus, and it is not easy to leave the first adhesive layer with a lower visible light transmittance on the upper part (image display side) of the light-emitting element. Therefore, the light-emitting efficiency of the light-emitting element can be improved.

[0071] Specifically, the storage modulus G1' of the first adhesive layer 1 at 90°C is, for example, about 1.0 kPa to about 35 kPa, and can be 1.0 kPa or more, 2.0 kPa or more, 3.0 kPa or more, or 4.0 kPa or more, and can be 35.0 kPa or less, 30.0 kPa or less, 25.0 kPa or less, or 20.0 kPa or less.

[0072] The storage modulus G2' of the second adhesive layer 2 at 90°C is, for example, about 30.0 kPa to about 800.0 kPa, and can be 30.0 kPa or more, 40.0 kPa or more, 50.0 kPa or more, or 60.0 kPa or more, and can be 800.0 kPa or less, 600.0 kPa or less, 400.0 kPa or less, or 300.0 kPa or less.

[0073] From the viewpoint of improving luminous efficiency, G1' and G2' preferably satisfy G1' / G2'<0.3. G1' / G2' is preferably 0.2 or less, more preferably 0.15 or less, particularly preferably 0.1 or less, and most preferably 0.05 or less. There is no particular restriction on the lower limit of G1' / G2', but from the viewpoint of encapsulation, it is preferably 0.001 or more.

[0074] G1' and G2' can be within a desired range by appropriately adjusting the type of monomer constituting the polymer contained in the pressure-sensitive adhesive layer described later and the amount of the cross-linking component added, for example.

[0075] The storage modulus refers to the storage modulus measured by the following method using a laminated product obtained by laminating the resin material (first adhesive layer or second adhesive layer) constituting the measured object part into 1 mm as a measurement sample. Specifically, the above-mentioned laminated product is cut into a diameter of 8 mm to prepare a test piece. Using a fixture with a diameter of 8 mm, a temperature dispersion of -50°C to 150°C is performed using a viscoelastic device ARES-G2 manufactured by TA Instruments. At this time, the heating rate is set to 5°C / min, the frequency is set to 1Hz, and the strain is set to 0.1%. The elastic modulus at 90°C at this time is taken as the storage modulus.

[0076] The storage modulus G'90°C of the first adhesive layer and the second adhesive layer at a temperature of 90°C is, for example, about 1 kPa to about 35 kPa, and may be 1 kPa or more, 2 kPa or more, 3 kPa or more, or 4 kPa or more, and may be 35 kPa or less, 30 kPa or less, 25 kPa or less, or 20 kPa or less. If the storage modulus of the adhesive layer at 90°C is within the above range, both appropriate softness and adhesiveness can be achieved.

[0077] Hereinafter, each structure of the pressure-sensitive adhesive sheet will be described in detail.

[0078] [Base material]

[0079] In an embodiment of the present invention, the substrate 3 is not particularly limited, and examples thereof include glass, a transparent plastic film substrate, and the like. The above-mentioned transparent plastic film substrate is not particularly limited, and a substrate having excellent visible light transmittance and excellent transparency (preferably a substrate having a haze value of 5% or less) is preferred. Examples thereof include the transparent plastic film substrate described in Japanese Patent Application Laid-Open No. 2008-90263. As the above-mentioned transparent plastic film substrate, a substrate having less optical birefringence is preferably used. In an embodiment of the present invention, the substrate 3 can be used, for example, as a protective member of a laminate. In this case, as the aforementioned transparent plastic film substrate, a film formed of triacetyl cellulose (TAC), polycarbonate, an acrylic polymer, a polyolefin having a cyclic or norbornene structure, or the like is preferred. In addition, in an embodiment of the present invention, the substrate 3 can also be the protective member itself. If such a structure is adopted, the process of separately laminating a protective member in the manufacture of the laminate can be reduced, so that the number of processes and necessary components can be reduced, and the production efficiency can be improved. In addition, if such a structure is adopted, the protective member can be made thinner. It should be noted that when the substrate 3 is a protective member, the surface 3a is the outermost surface of the laminate.

[0080] In order to improve the adhesiveness, retention, etc. with the adhesive, the surface of the above-mentioned substrate on the side having the above-mentioned adhesive layer can be subjected to physical treatments such as corona discharge treatment, plasma treatment, sandblasting treatment, ozone exposure treatment, flame exposure treatment, high-voltage electric shock exposure treatment, ionization radiation treatment, etc.; chemical treatments such as chromic acid treatment; surface treatments such as easy adhesion treatment using a coating agent (primer). The surface treatment for improving adhesiveness and retention is preferably performed on the entire surface of the substrate on the adhesive layer side.

[0081] In the adhesive sheet of the present embodiment, it is preferred that the visible light transmittance T1 of the first adhesive layer 1 and the visible light transmittance T3 of the substrate 3 satisfy T1 < T3. This configuration is a configuration in which the substrate 3 having a visible light transmittance higher than that of the first adhesive layer 1 is located above the light-emitting element (image display side), which can improve the light-emitting efficiency and brighten the image, and can reduce the power consumption caused by the increase in output power for improving the light-emitting brightness. In this regard, it is preferred. The visible light transmittance T3 of the substrate 3 is not particularly limited, and is, for example, 85% to 100%, and can be 88% or more, 90% or more, or 92% or more.

[0082] In an embodiment of the present invention, the thickness of the substrate 3 is not particularly limited. Considering workability such as strength and operability, and thin layer properties, etc., it is preferably in the range of 10 μm to 500 μm. More preferably, it is in the range of 20 μm to 300 μm, and most preferably, it is in the range of 100 μm to 200 μm. The refractive index of the above-mentioned substrate 3 is not particularly limited, and is, for example, in the range of 1.30 to 1.80, and preferably in the range of 1.40 to 1.70.

[0083] In the embodiment of the present invention, the surface 3a of the substrate 3 is preferably subjected to a reflective surface treatment and / or an anti-glare treatment. When the surface 3a of the substrate 3 is subjected to a reflective surface treatment and / or an anti-glare treatment, the surface 3a becomes the outermost surface of the laminate, which can prevent the reduction of visual recognition caused by reflection of external light, reflection of images, etc., or can adjust the appearance such as glossiness. The anti-glare treatment is preferably easy to manufacture and low in cost.

[0084] [Adhesive layer]

[0085] In the embodiment of the present invention, at least one of the first adhesive layer 1 and the second adhesive layer 2 is preferably an adhesive layer formed of an adhesive composition selected from a photocurable adhesive composition and a solvent-based adhesive composition.

[0086] In the embodiment of the present invention, the first adhesive layer 1 and the second adhesive layer 2 may be both adhesive layers formed of a photocurable adhesive composition, or both adhesive layers formed of a solvent-based adhesive composition. In addition, one may be an adhesive layer formed of a photocurable adhesive composition and the other may be an adhesive layer formed of another adhesive composition, or one may be an adhesive layer formed of a solvent-based adhesive composition and the other may be an adhesive layer formed of another adhesive composition.

[0087] In the embodiment of the present invention, the first adhesive layer 1 is preferably an adhesive layer formed of a solvent-based adhesive composition.

[0088] For example, when the adhesive sheet of an embodiment of the present invention is used for packaging a substrate having a light-emitting element as a chip component, the thickness of the first adhesive layer 1 is preferably about 0.5 μm to about 30 μm from the viewpoint of not easily leaving the first adhesive layer on the upper part (image display side) of the light-emitting element while fully packaging the substrate.

[0089] On the other hand, the second adhesive layer 2 may be an adhesive layer formed of a photocurable adhesive composition or an adhesive layer formed of a solvent-based adhesive composition.

[0090] The adhesive composition for forming the first adhesive layer 1 preferably contains a colorant. That is, the first adhesive layer 1 preferably contains a colorant. When the adhesive composition for forming the first adhesive layer 1 contains a colorant, the light transmittance of the first adhesive layer 1 decreases, which is preferable in terms of the configuration where T1 < T2 is satisfied for T1 and T2. The first adhesive layer 1 with reduced light transmittance and imparted light-shielding property encapsulates between the metal wiring layer 6 and the LED chip of the laminate (micro LED display device) of the embodiment of the present invention, preventing reflection caused by the metal wiring, etc., preventing color mixing between LED chips, and improving the contrast of the image.

[0091] The adhesive composition for forming the first adhesive layer 1 is preferably a solvent-based adhesive composition containing a colorant, and as the colorant, carbon black is preferably listed among the colorants described later.

[0092] That is, the colorant contained in the first adhesive layer 1 preferably contains carbon black.

[0093] The adhesive composition for forming the second adhesive layer 2 may contain a colorant, and from the viewpoint of the configuration where T1 and T2 satisfy T1 < T2, it preferably does not contain a colorant. That is, the second adhesive layer 2 preferably does not contain a colorant.

[0094] <<Photo-curable adhesive composition>>

[0095] The photo-curable adhesive composition preferably contains a polymer, a photo-polymerizable compound, and a photo-polymerization initiator.

[0096] The adhesive layer formed using the photo-curable adhesive composition is roughly classified into a type of adhesive layer that undergoes photo-curing (first form) and a type that does not undergo photo-curing and undergoes photo-curing after lamination as described later (second form).

[0097] For example, both the first adhesive layer 1 and the second adhesive layer 2 of the embodiment of the present invention can be adhesive layers of the first form, or both can be adhesive layers of the second form. In addition, one can be an adhesive layer of the first form and the other can be another adhesive layer, or one can be an adhesive layer of the second form and the other can be another adhesive layer.

[0098] <First form>

[0099] The adhesive layer of the first form can be formed by coating a photo-curable adhesive composition containing a polymer, a photo-polymerizable compound, and a photo-polymerization initiator on a release liner and performing photo-curing.

[0100] (Polymer)

[0101] Examples of the polymer contained in the photocurable adhesive composition include acrylic polymers, polysiloxane polymers, polyesters, polyurethanes, polyamides, polyvinyl ethers, vinyl acetate / vinyl chloride copolymers, modified polyolefins, epoxy polymers, fluorine-containing polymers, natural rubbers, synthetic rubbers and other rubber-based polymers. In particular, acrylic polymers are preferably used because they exhibit appropriate adhesive properties such as wettability, cohesiveness and tackiness, and are also excellent in weather resistance, heat resistance and the like.

[0102] The acrylic polymer contains an alkyl (meth)acrylate as a main monomer component. It should be noted that in this specification, "(meth)acrylic acid" refers to acrylic acid and / or methacrylic acid. The amount of the alkyl (meth)acrylate is preferably 50% by mass or more, more preferably 55% by mass or more, and further preferably 60% by mass or more relative to the total amount of monomer components constituting the acrylic polymer.

[0103] As the alkyl (meth)acrylate, there is suitably used an alkyl (meth)acrylate in which the carbon number of the alkyl group is 1 to 20. The alkyl group of the alkyl (meth)acrylate may have a branched chain, and the alkyl (meth)acrylate may have a cyclic alkyl group.

[0104] Specific examples of the (meth)acrylic acid alkyl ester having a chain alkyl group include methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, pentyl (meth)acrylate, isopentyl (meth)acrylate, neopentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, propylene (meth)acrylate, octyl ... Nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, isotridecyl (meth)acrylate, tetradecyl (meth)acrylate, isotetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, isooctadecyl (meth)acrylate, nonadecyl (meth)acrylate, etc. Preferred alkyl (meth)acrylates having a chain alkyl group used in the first embodiment are butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, octadecyl (meth)acrylate, and dodecyl (meth)acrylate. The amount of the alkyl (meth)acrylate having a chain alkyl group relative to the total amount of the monomer components constituting the acrylic polymer is, for example, about 40% to about 90% by mass, and can be 45% to 80% by mass or 50% to 70% by mass.

[0105] Specific examples of the alkyl (meth)acrylate having an alicyclic alkyl group include: cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, cycloheptyl (meth)acrylate, cyclooctyl (meth)acrylate and other cycloalkyl (meth)acrylates; isobornyl (meth)acrylate and other (meth)acrylates having a dicyclic aliphatic hydrocarbon ring; tetrahydrodicyclopentadienyl (meth)acrylate, tetrahydrodicyclopentadienyloxyethyl (meth)acrylate, tetrahydrotricyclopentadienyl (meth)acrylate, 1-adamantyl (meth)acrylate, 2-methyl-2-adamantyl (meth)acrylate, 2-ethyl-2-adamantyl (meth)acrylate and other (meth)acrylates having an aliphatic hydrocarbon ring of three or more rings. Preferred alkyl (meth)acrylates having an alicyclic alkyl group used in the first embodiment are cyclohexyl (meth)acrylate and isobornyl (meth)acrylate. The amount of the alkyl (meth)acrylate having an alicyclic alkyl group is, for example, about 3 to 50 mass %, 5 to 40 mass %, or 10 to 30 mass % relative to the total amount of monomer components constituting the acrylic polymer.

[0106] The acrylic polymer may contain polar group-containing monomers such as hydroxyl-containing monomers, carboxyl-containing monomers, and nitrogen-containing monomers as constituent monomer components. The acrylic polymer contains polar group-containing monomers as constituent monomer components, which has a tendency to increase the cohesive force of the adhesive and increase the adhesive force. The preferred polar group-containing monomers used in the first form are hydroxyl-containing monomers and nitrogen-containing monomers. Relative to the total amount of monomer components constituting the acrylic polymer, the amount of polar group-containing monomers (the total of hydroxyl-containing monomers, carboxyl-containing monomers, and nitrogen-containing monomers) is, for example, about 3% to about 50% by mass, and can be 5% to 40% by mass or 10% to 30% by mass.

[0107] As hydroxyl-containing monomers, there can be cited: (meth) 2-hydroxyethyl acrylate, (meth) 2-hydroxypropyl acrylate, (meth) 4-hydroxybutyl acrylate, (meth) 6-hydroxyhexyl acrylate, (meth) 8-hydroxyoctyl acrylate, (meth) 10-hydroxydecyl acrylate, (meth) 12-hydroxylauryl acrylate, (meth) methyl acrylate (4-hydroxymethylcyclohexyl) acrylate and other (meth) acrylates. In the case of introducing a cross-linked structure into a polymer by an isocyanate cross-linking agent, the hydroxyl group can become a reaction site (cross-linking site) with an isocyanate group. As preferred hydroxyl-containing monomers used in the first form, 2-hydroxyethyl (meth) acrylate and 4-hydroxybutyl (meth) acrylate. Relative to the total amount of monomer components constituting the acrylic polymer, the amount of the hydroxyl-containing monomer is, for example, about 3% to about 50% by mass, and can be 5% to 40% by mass or 10% to 30% by mass.

[0108] As carboxyl-containing monomers, there can be cited: acrylic monomers such as (meth)acrylic acid, (meth)carboxyethyl acrylate, (meth)carboxypentyl acrylate, itaconic acid, maleic acid, fumaric acid, crotonic acid, etc. In the case of introducing a cross-linked structure into a polymer by an epoxy cross-linking agent, the carboxyl group can become a reaction site (cross-linking site) with an epoxy group. As a preferred carboxyl-containing monomer used in the first form, (meth)acrylic acid. Relative to the total amount of monomer components constituting the acrylic polymer, the amount of the carboxyl-containing monomer is, for example, about 3% to about 50% by mass, and can be 5% to 40% by mass or 10% to 30% by mass.

[0109] Examples of the nitrogen-containing monomer include N-vinylpyrrolidone, methylvinylpyrrolidone, vinylpyridine, vinylpiperidone, vinylpyrimidine, vinylpiperazine, vinylpyrazine, vinylpyrrole, vinylimidazole, vinyl The preferred nitrogen-containing monomer used in the first embodiment is N-vinyl pyrrolidone. The amount of the nitrogen-containing monomer is, for example, about 3% to about 50% by mass, and can be 5% to 40% by mass or 10% to 30% by mass relative to the total amount of monomer components constituting the acrylic polymer.

[0110] The acrylic polymer may contain the following monomers as monomer components other than the above (sometimes referred to as "other monomers"): vinyl monomers such as acid anhydride group-containing monomers, caprolactone adducts of (meth)acrylic acid, sulfonic acid group-containing monomers, phosphoric acid group-containing monomers, vinyl acetate, vinyl propionate, styrene, and α-methylstyrene; epoxy group-containing monomers such as glycidyl (meth)acrylate; glycol acrylate monomers such as polyethylene glycol (meth)acrylate, polypropylene glycol (meth)acrylate, methoxyethylene glycol (meth)acrylate, and methoxypolypropylene glycol (meth)acrylate; acrylate monomers such as tetrahydrofurfuryl (meth)acrylate, fluorine-containing (meth)acrylate, polysiloxane (meth)acrylate, and 2-methoxyethyl (meth)acrylate, etc.

[0111] The glass transition temperature (Tg) of the polymer contained in the photocurable adhesive composition is preferably 0° C. or lower. The glass transition temperature of the polymer may be -5° C. or lower, -10° C. or lower, or -15° C. or lower.

[0112] The glass transition temperature of a polymer is the peak temperature of the dielectric loss tangent (tanδ) obtained by dynamic viscoelasticity measurement. When a cross-linked structure is introduced into a polymer, the glass transition temperature can be calculated based on the theoretical Tg according to the composition of the polymer. The theoretical Tg is calculated by the Fox formula described below.

[0113] The polymer can be obtained by polymerizing the above-mentioned monomer components by various known methods. The polymerization method is not particularly limited.

[0114] In the preparation of the adhesive layer of the first form, it is preferred to prepare a polymer (prepolymer) with a low degree of polymerization in which a part of the monomer components is unreacted and remains. The composition for preparing the prepolymer (prepolymer forming composition) preferably contains a photopolymerization initiator in addition to the monomer. The photopolymerization initiator can be appropriately selected according to the type of monomer. For example, a photo radical polymerization initiator is used in the polymerization of acrylic polymers. As the photopolymerization initiator, benzoin ether photopolymerization initiators, acetophenone photopolymerization initiators, α-ketol photopolymerization initiators, aromatic sulfonyl chloride photopolymerization initiators, photoactive oxime photopolymerization initiators, benzoin photopolymerization initiators, benzyl photopolymerization initiators, benzophenone photopolymerization initiators, ketal photopolymerization initiators, thioxanthone photopolymerization initiators, acylphosphine oxide photopolymerization initiators, etc. can be listed.

[0115] During polymerization, a chain transfer agent, a polymerization inhibitor (polymerization retardant), etc. may be used to adjust the molecular weight, etc. Examples of the chain transfer agent include mercaptans such as α-thioglycerol, lauryl mercaptan, glycidyl mercaptan, thioglycolic acid, 2-mercaptoethanol, thioglycolic acid, 2-ethylhexyl thioglycolate, and 2,3-dimercapto-1-propanol, and α-methylstyrene dimer.

[0116] The polymerization rate of the prepolymer is not particularly limited. From the perspective of a viscosity suitable for coating on a substrate, it is preferably 3% to 50%, and more preferably 5% to 40%. The polymerization rate of the prepolymer can be adjusted within the desired range by adjusting the type and amount of the photopolymerization initiator; the irradiation intensity and irradiation time of active light such as UV light, etc. The polymerization rate of the prepolymer is the non-volatile component when heated at 130°C for 3 hours, and is calculated by the following formula. The polymerization rate (non-volatile component) of the adhesive layer is also measured by the same method.

[0117] Polymerization rate (%) = mass after heating / mass before heating × 100

[0118] As described above, the photocurable adhesive composition for forming the adhesive layer contains a polymer, a photopolymerizable compound and a photopolymerization initiator. For example, the photocurable adhesive composition is obtained by adding a photopolymerizable compound and a photopolymerization initiator to a prepolymer. Alternatively, a low molecular weight polymer (oligomer) may be used instead of a prepolymer, and a photopolymerizable compound, a photopolymerization initiator and a colorant may be mixed in the low molecular weight polymer to prepare the photocurable adhesive composition.

[0119] (Photopolymerizable compound)

[0120] The photopolymerizable compound contained in the above-mentioned photocurable adhesive composition has one or more photopolymerizable functional groups in one molecule. The photopolymerizable functional group can be any one of a free radical polymerizable functional group, a cationic polymerizable functional group and an anionic polymerizable functional group. From the perspective of excellent reactivity, a free radical polymerizable functional group having an unsaturated double bond (ethylenically unsaturated group) is preferred.

[0121] The prepolymer contains a polymer and unreacted monomers, and the unreacted monomers remain photopolymerizable. Therefore, in the preparation of the photocurable adhesive composition, it is not necessarily necessary to add a photopolymerizable compound. When a photopolymerizable compound is added to the prepolymer, the added photopolymerizable compound may be the same as or different from the monomer used in the preparation of the prepolymer.

[0122] When the polymer is an acrylic polymer, from the perspective of high compatibility with the polymer, the compound added as the photopolymerizable compound is preferably a monomer or oligomer having a (meth)acryloyl group as the photopolymerizable functional group. The photopolymerizable compound may be a polyfunctional compound having two or more photopolymerizable functional groups in one molecule. Examples of the photopolymerizable polyfunctional compound include polyfunctional (meth)acrylates. Examples of the polyfunctional (meth)acrylate include difunctional (meth)acrylates such as polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, polytetramethylene glycol di(meth)acrylate, bisphenol A ethylene oxide-modified di(meth)acrylate, bisphenol A propylene oxide-modified di(meth)acrylate, alkylene glycol di(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, pentaerythritol di(meth)acrylate, neopentyl glycol di(meth)acrylate, glycerol di(meth)acrylate, and urethane di(meth)acrylate; trifunctional (meth)acrylates such as pentaerythritol tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, and ethoxylated isocyanuric acid tri(meth)acrylate; tetrafunctional (meth)acrylates such as di(trimethylolpropane) tetra(meth)acrylate, ethoxylated pentaerythritol tetra(meth)acrylate, and pentaerythritol tetra(meth)acrylate; and pentafunctional or higher (meth)acrylates such as dipentaerythritol penta(meth)acrylate and dipentaerythritol hexa(meth)acrylate.

[0123] In the photocurable adhesive composition for forming the first adhesive layer, when a polyfunctional compound is used as the photopolymerizable compound, the amount of the polyfunctional compound used is preferably 10 parts by mass or less, more preferably 0.001 to 1 part by mass, and further preferably 0.005 to 0.5 part by mass, based on 100 parts by mass of the polymer (including the prepolymer). When the amount of the polyfunctional compound used is too large, the viscosity of the adhesive layer after photocuring may be low and the adhesive strength may be poor. In addition, it may be difficult to achieve the configuration where G1’ and G2’ satisfy G1’ < G2’. The amount of the polyfunctional compound used may be 10 parts by mass or less, 5 parts by mass or less, 3 parts by mass or less, or 1 part by mass or less. The amount of the polyfunctional compound used may be 0.001 part by mass or more, 0.01 part by mass or more, or 0.1 part by mass or more.

[0124] In the photocurable adhesive composition for forming the second adhesive layer, when a polyfunctional compound is used as the photopolymerizable compound, the amount of the polyfunctional compound used is preferably 10 parts by mass or less, more preferably 0.1 to 8 parts by mass, and still more preferably 1.1 to 6 parts by mass, based on 100 parts by mass of the polymer (including prepolymer). When the amount of the polyfunctional monomer used is too large, the viscosity of the adhesive layer after photocuring may be low and the adhesive strength may be poor. The amount of the polyfunctional compound used may be 10 parts by mass or less, 8 parts by mass or less, or 6 parts by mass or less. Considering the aspect of forming a structure in which the above G1' and G2' satisfy G1' < G2', the amount of the polyfunctional monomer used may be 0.1 part by mass or more, 1.1 parts by mass or more, or 2 parts by mass or more.

[0125] When a monomer for forming a prepolymer is used as the photopolymerizable compound, a hydroxy group-containing monomer is preferred, and 2-hydroxyethyl (meth)acrylate and 4-hydroxybutyl (meth)acrylate are more preferred. When a hydroxy group-containing monomer is used as the photopolymerizable compound, the amount of the hydroxy group-containing monomer used is preferably 40 parts by mass or less, more preferably 1 to 30 parts by mass, and still more preferably 5 to 20 parts by mass, based on 100 parts by mass of the polymer (including prepolymer). The amount of the hydroxy group-containing monomer used may be 40 parts by mass or less, 30 parts by mass or less, or 20 parts by mass or less. The amount of the hydroxy group-containing monomer used may be 0 part by mass, or may be 1 part by mass or more, 5 parts by mass or more, or 10 parts by mass or more.

[0126] (Photoinitiator)

[0127] The photocurable adhesive composition contains a photoinitiator. The photoinitiator generates free radicals, acids, bases, etc. by irradiation with active light such as ultraviolet rays, and can be appropriately selected according to the type of the photopolymerizable compound. When the photopolymerizable compound is a compound having a (meth)acryloyl group (for example, monofunctional or polyfunctional (meth)acrylate), a photo radical polymerization initiator is preferably used as the photoinitiator. The photoinitiator can be used alone or in combination of two or more.

[0128] When the photoinitiator used in the preparation (polymerization) of the above polymer (including prepolymer) remains without inactivation, the addition of the photoinitiator can be omitted. When a photoinitiator is added to the polymer, the added photoinitiator can be the same as or different from the photoinitiator used for preparing the polymer.

[0129] The photopolymerization initiator contained in the photocurable adhesive composition preferably has a maximum absorption in a wavelength region where the light absorption caused by the colorant described later is small. Specifically, the photopolymerization initiator preferably has a maximum absorption in the wavelength range of 330nm to 400nm. By making the photopolymerization initiator have a maximum absorption in a region where the light absorption caused by the colorant is small, the curing hindrance caused by the colorant is suppressed, so the polymerization rate can be fully increased by photocuring. Examples of the photoradical polymerization initiator having a maximum absorption in the wavelength range of 330nm to 400nm include: hydroxy ketones, benzil dimethyl ketals, amino ketones, acyl phosphine oxides, benzophenones, trichloromethyl-containing triazine derivatives, and the like.

[0130] The content of the photopolymerization initiator in the photocurable adhesive composition is about 0.01 to 10 parts by mass, preferably about 0.05 to 5 parts by mass, based on 100 parts by mass of the total monomers (monomers used in the preparation of the polymer and photopolymerizable compounds added to the polymer).

[0131] (Colorant)

[0132] The photocurable adhesive composition used in the embodiment of the present invention may contain a colorant. In particular, the photocurable adhesive composition forming the first adhesive layer 1 preferably contains a colorant.

[0133] As long as the colorant can be dissolved or dispersed in the photocurable adhesive composition, it can be either a dye or a pigment. From the perspective of being able to achieve low haze even when added in small amounts, and being easy to be evenly distributed without sedimentation like a pigment, a dye is preferred. In addition, from the perspective of having high color development even when added in small amounts, a pigment is preferred. When a pigment is used as a colorant, a pigment with low or no conductivity is preferred. In addition, when a dye is used, it is preferably used in combination with an antioxidant described later.

[0134] There are no particular restrictions on the colorant used in the embodiment of the present invention, but a colorant that absorbs visible light and has ultraviolet transmittance is preferred. That is, the colorant is preferably a colorant whose average transmittance at a wavelength of 330nm to 400nm is greater than the average transmittance at a wavelength of 400nm to 700nm. The transmittance of the colorant is measured using a solution or a dispersion, which is diluted with an appropriate solvent or dispersion medium (an organic solvent with low absorption in the range of wavelengths of 330nm to 700nm) such as tetrahydrofuran (THF) until the transmittance at a wavelength of 400nm becomes about 50% to about 60%.

[0135] Examples of ultraviolet-transmitting black pigments that absorb less ultraviolet light than visible light include "9050 BLACK" and "UVBK-0001" manufactured by Tokushiki. Examples of ultraviolet-transmitting black dyes include "SOC-L-0123" manufactured by Orient Chemical Industries.

[0136] Carbon black and titanium black, which are commonly used as black colorants, absorb more ultraviolet light than visible light (ultraviolet transmittance is lower than visible light transmittance). Therefore, when a colorant such as carbon black is added to a photocurable adhesive composition that is sensitive to ultraviolet light, most of the ultraviolet light irradiated for photocuring is absorbed by the colorant, the amount of light absorbed by the photopolymerization initiator is small, and photocuring requires time (the cumulative amount of irradiated light increases). In addition, when the thickness of the adhesive layer is large, less ultraviolet light reaches the surface on the opposite side of the light irradiation surface, so there is a tendency that photocuring is insufficient even if light irradiation is performed for a long time. In contrast, by using a colorant whose ultraviolet transmittance is greater than that of visible light, it is possible to suppress the curing hindrance caused by the colorant.

[0137] The content of the colorant in the photocurable adhesive composition forming the first adhesive layer is, for example, about 0.01 to about 20 parts by mass relative to 100 parts by mass of the total amount of the monomers, and the content of the colorant in the photocurable adhesive composition forming the first adhesive layer can be appropriately set according to the type of the colorant, the color tone and light transmittance of the adhesive layer, etc. The colorant can be added to the composition in the form of a solution or dispersion obtained by dissolving or dispersing it in an appropriate solvent.

[0138] The photocurable adhesive composition forming the second adhesive layer of the embodiment of the present invention preferably does not contain a colorant. By forming the photocurable adhesive composition of the second adhesive layer without a colorant, the transmittance to visible light becomes higher, and the luminous efficiency of the laminate (micro LED display device) is improved. In the case where the photocurable adhesive composition forming the second adhesive layer contains a colorant, its content is, for example, less than about 0.1 parts by mass relative to 100 parts by mass of the total amount of monomers. Even in the case where a colorant is not added to the photocurable adhesive composition forming the second adhesive layer, there may be a situation where the colorant added to the first adhesive layer is transferred to the second adhesive layer.

[0139] (Silane coupling agent)

[0140] The photocurable adhesive composition used in the embodiment of the present invention may contain a silane coupling agent within the scope of not impairing the effect of the present invention. When the photocurable adhesive composition contains a silane coupling agent, the adhesion reliability to glass (especially the adhesion reliability to glass under high temperature and high humidity environment) is improved, which is preferred.

[0141] As the silane coupling agent, there is no particular limitation, and preferably, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropyltriethoxysilane, γ-aminopropyltrimethoxysilane, N-phenyl-aminopropyltrimethoxysilane, 3-acryloxypropyltrimethoxysilane, etc. can be cited. Among them, γ-glycidoxypropyltrimethoxysilane is preferred. In addition, as a commercial product, for example, the trade name "KBM-403" (manufactured by Shin-Etsu Chemical Co., Ltd.) can be cited. It should be noted that the silane coupling agent can be used alone or in combination of two or more.

[0142] The content of the silane coupling agent in the photocurable adhesive composition is not particularly limited, but is preferably 0.01 to 1 part by mass, more preferably 0.03 to 0.5 parts by mass, based on 100 parts by mass of the polymer.

[0143] (Other ingredients)

[0144] In the first form, the photocurable adhesive composition may contain ingredients other than polymers, photopolymerizable compounds, photopolymerization initiators and colorants. For example, a chain transfer agent may be contained for the purpose of adjusting the photocuring speed. In addition, in order to adjust the viscosity of the above-mentioned photocurable adhesive composition, adjust the adhesion of the adhesive layer, etc., oligomers and tackifiers may be contained. As an oligomer, for example, an oligomer with a weight average molecular weight of about 1000 to about 30000 is used. As an oligomer, acrylic oligomers are preferred from the aspect of excellent compatibility with acrylic polymers. The above-mentioned photocurable adhesive composition may contain additives such as plasticizers, softeners, anti-deterioration agents, fillers, antioxidants, surfactants, antistatic agents, etc.

[0145] <Second Form>

[0146] The second form of the adhesive layer is a type of adhesive layer that is not photocured, and the photocurable adhesive composition can be formed into a sheet. The second form of the adhesive layer contains a photopolymerizable compound in an unreacted state, so the adhesive layer can be photocurable.

[0147] The photocurable adhesive composition used for forming the adhesive layer of the second embodiment preferably contains a polymer, a photopolymerizable compound, and a photopolymerization initiator.

[0148] (polymer)

[0149] As the polymer contained in the pressure-sensitive adhesive composition, various polymers can be applied as in the first embodiment, but an acrylic polymer is preferably used. The monomer components constituting the acrylic polymer are the same as in the first embodiment.

[0150] In order to introduce a crosslinked structure using a crosslinking agent described later, the monomer components constituting the polymer preferably include a hydroxyl-containing monomer and / or a carboxyl-containing monomer. For example, when an isocyanate crosslinking agent is used, a hydroxyl-containing monomer is preferably contained as a monomer component. When an epoxy crosslinking agent is used, a carboxyl-containing monomer is preferably contained as a monomer.

[0151] In the second embodiment, since photocuring is not performed on the substrate, a polymer with a relatively large molecular weight is used as the polymer contained in the photocurable adhesive composition to form a solid (fixed) adhesive layer. The weight average molecular weight of the polymer is, for example, about 100,000 to about 2,000,000.

[0152] Since the high molecular weight polymer is solid, the adhesive composition is preferably a solution of the polymer dissolved in an organic solvent. For example, the polymer solution is obtained by solution polymerization of the monomer components. The polymer solution can also be prepared by dissolving a solid polymer in an organic solvent.

[0153] As a solvent for solution polymerization, for example, ethyl acetate, toluene, etc. are used. The solution concentration is generally about 20% to about 80% by mass. As a polymerization initiator, it is preferred to use azo initiators, peroxide initiators, redox initiators (for example, a combination of persulfate and sodium bisulfite, a combination of peroxide and sodium ascorbate) and other thermal polymerization initiators. The amount of the polymerization initiator is not particularly limited, for example, relative to 100 parts by mass of the total amount of the monomer components forming the polymer, preferably about 0.005 parts by mass to about 5 parts by mass, more preferably 0.02 parts by mass to 3 parts by mass.

[0154] (Photopolymerizable compound)

[0155] The photopolymerizable compound contained in the pressure-sensitive adhesive composition in the second embodiment is the same as those described above with respect to the first embodiment, and a compound having one or two or more photopolymerizable functional groups can be used.

[0156] (Photopolymerization Initiator)

[0157] The photopolymerization initiator contained in the adhesive composition in the second embodiment is the same as the photopolymerization initiator described in the first embodiment, and preferably has a maximum absorption in the wavelength range of 330nm to 400nm. The amount of the photopolymerization initiator is about 0.01 to 10 parts by mass, preferably about 0.05 to 5 parts by mass, relative to 100 parts by mass of the polymer.

[0158] (Colorant)

[0159] The adhesive composition used in the second embodiment may contain a colorant. In particular, it is preferred that the photocurable adhesive composition forming the first adhesive layer 1 further contains a colorant.

[0160] The colorant contained in the adhesive composition used in the second embodiment is the same as the colorant described in the first embodiment, and is preferably a colorant having an average transmittance at a wavelength of 330 nm to 400 nm greater than an average transmittance at a wavelength of 400 nm to 700 nm.

[0161] (Crosslinking agent)

[0162] The second form of the adhesive composition preferably contains a crosslinking agent that can crosslink with the above polymer. Specific examples of the crosslinking agent for introducing a crosslinking structure into the polymer include isocyanate crosslinking agents, epoxy crosslinking agents, Azoline crosslinking agent, aziridine crosslinking agent, peroxide crosslinking agent, carbodiimide crosslinking agent, metal chelate crosslinking agent, etc. Among them, isocyanate crosslinking agent and epoxy crosslinking agent are preferred from the viewpoint of high reactivity with hydroxyl and carboxyl groups of polymer and easy introduction of crosslinked structure. These crosslinking agents react with functional groups such as hydroxyl and carboxyl groups introduced into polymer to form crosslinked structure.

[0163] As an isocyanate crosslinking agent, a polyisocyanate having two or more isocyanate groups in one molecule is used. Examples of isocyanate crosslinking agents include: low-order aliphatic polyisocyanates such as butylene diisocyanate and hexamethylene diisocyanate; alicyclic isocyanates such as cyclopentylene diisocyanate, cyclohexylene diisocyanate, and isophorone diisocyanate; aromatic isocyanates such as 2,4-toluene diisocyanate, 4,4'-diphenylmethane diisocyanate, and xylylene diisocyanate; trimethylolpropane / toluene diisocyanate trimer adducts (e.g., "Coronate L" manufactured by Tosoh), trimethylolpropane / hexamethylene diisocyanate trimer adducts (e.g., "Coronate HL" manufactured by Tosoh), trimethylolpropane adducts of xylylene diisocyanate (e.g., "Takenate 1" manufactured by Mitsui Chemicals), and the like. D110N", isocyanate adducts such as isocyanurate of hexamethylene diisocyanate (for example, "Coronate HX" manufactured by Tosoh Corporation), and the like.

[0164] As the epoxy crosslinking agent, a polyfunctional epoxy compound having two or more epoxy groups in one molecule is used. The epoxy group of the epoxy crosslinking agent may be a glycidyl group. Examples of the epoxy crosslinking agent include N,N,N',N'-tetraglycidyl-m-xylylenediamine, diglycidyl aniline, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, 1,6-hexanediol diglycidyl ether, neopentyl glycol diglycidyl ether, ethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, sorbitol polyglycidyl ether, glycerol polyglycidyl ether, pentaerythritol polyglycidyl ether, polyglycerol polyglycidyl ether, sorbitan polyglycidyl ether, trimethylolpropane polyglycidyl ether, adipic acid diglycidyl ester, phthalic acid diglycidyl ester, triglycidyl-tris(2-hydroxyethyl)isocyanurate, resorcinol diglycidyl ether, and bisphenol S diglycidyl ether. As the epoxy crosslinking agent, commercially available products such as "Denacol" manufactured by Nagase Chemte X, "Tetrad X" and "Tetrad C" manufactured by Mitsubishi Gas Chemical can be used.

[0165] The amount of the crosslinking agent is about 0.01 to 5 parts by mass, and may be 0.05, 0.1 or 0.2 parts by mass or less, and may be 3, 2 or 1 part by mass or less, relative to 100 parts by mass of the polymer.

[0166] (Other ingredients)

[0167] The second form of the PSA composition may contain, in addition to the above-mentioned components, oligomers, tackifiers, silane coupling agents, chain transfer agents, plasticizers, softeners, anti-degradation agents, fillers, antioxidants, surfactants, antistatic agents, and the like.

[0168] <<Solvent-based adhesive composition>>

[0169] In an embodiment of the present invention, at least one of the first adhesive layer 1 and the second adhesive layer 2 may be an adhesive layer formed of a solvent-based adhesive composition (third form). The above-mentioned solvent-based adhesive composition contains at least a polymer and a solvent, and may contain a cross-linking agent. That is, the solvent-based adhesive composition used in the formation of the adhesive layer of the third form contains a polymer and a solvent, and may contain a cross-linking agent as needed.

[0170] The form of the solvent-based adhesive composition is not particularly limited. For example, there can be cited an adhesive composition in which the adhesive component is contained in an organic solvent (solvent-based adhesive composition), an adhesive composition in which the adhesive component is dispersed in an aqueous solvent (aqueous dispersion-based adhesive composition, typically an aqueous emulsion-based adhesive composition), an adhesive composition in which the adhesive component is dissolved in water (aqueous solution-based adhesive composition), etc.

[0171] The solvent-based PSA composition according to the embodiment of the present invention is preferably in a form other than an aqueous emulsion-based PSA composition, preferably a solvent-based PSA composition or an aqueous solution-based PSA composition, and more preferably a solvent-based PSA composition.

[0172] <Third Form>

[0173] The third embodiment of the PSA layer can be formed by applying a solvent-based PSA composition containing a polymer and a solvent and, if necessary, a cross-linking agent onto a release liner and removing the solvent by drying.

[0174] (polymer)

[0175] As the polymer contained in the solvent-based PSA composition, various polymers can be applied as in the first embodiment, and an acrylic polymer is preferably used. The monomer components constituting the acrylic polymer are the same as in the first embodiment.

[0176] In the third embodiment, in order to form a solid (fixed) PSA layer on the substrate, a polymer with a relatively large molecular weight is used as the polymer contained in the solvent-based PSA composition. The weight average molecular weight of the polymer is, for example, about 100,000 to about 2,000,000.

[0177] Specific examples of the (meth)acrylic acid alkyl ester having a chain alkyl group as a monomer component constituting the acrylic polymer include the same examples as those in the first embodiment, and the preferred examples are also the same.

[0178] The amount of the (meth)acrylic acid alkyl ester having a chain alkyl group is typically greater than 50% by mass, for example, 70% by mass or more, 85% by mass or more, or 90% by mass or more relative to the total amount of the monomer components constituting the acrylic polymer. In addition, it is typically less than 100% by mass, and from the viewpoint of cohesive force, it is usually appropriate to be 99.5% by mass or less, and it may be 98% by mass or less (for example, less than 97% by mass).

[0179] Specific examples of the (meth)acrylic acid alkyl ester having an alicyclic alkyl group as a monomer component constituting the acrylic polymer include the same examples as those in the first embodiment, and the preferred examples are also the same.

[0180] The amount of the alkyl (meth)acrylate having an alicyclic alkyl group is, for example, about 3 to 50 mass %, 5 to 40 mass %, or 10 to 30 mass % relative to the total amount of monomer components constituting the acrylic polymer.

[0181] Specific examples of the hydroxyl group-containing monomer, carboxyl group-containing monomer, and nitrogen-containing monomer as the monomer component constituting the acrylic polymer include the same examples as those in the first embodiment, and the preferred examples are also the same.

[0182] The amount of the polar group-containing monomer may be, for example, 0.1% by mass or more, and is usually 0.5% by mass or more, and may be 1% by mass or more, relative to the total amount of the monomer components constituting the acrylic polymer. In addition, the amount of the polar group-containing monomer may be usually 40% by mass or less, preferably 20% by mass or less, and may be 10% by mass or less (e.g., 5% by mass or less), relative to the total amount of the monomer components.

[0183] The acrylic polymer may contain other monomer components, and specific examples of other monomers include the same examples as those in the first embodiment.

[0184] The glass transition temperature (Tg) of the polymer contained in the solvent-based adhesive composition forming the first adhesive layer is preferably designed to be, for example, -50°C to -30°C. In addition, the glass transition temperature (Tg) of the polymer contained in the solvent-based adhesive composition forming the second adhesive layer is preferably designed to be, for example, -30°C to 10°C. It is preferred that the Tg of the polymer is within the above range in order to make the storage modulus of the obtained adhesive layer within the above preferred range.

[0185] Here, the Tg of a polymer refers to the peak temperature of the dielectric loss tangent (tanδ) obtained by dynamic viscoelasticity measurement. In the case of introducing a cross-linked structure into a polymer, the Tg can be calculated based on the theoretical Tg according to the polymer composition. The theoretical Tg is calculated by the Fox formula. The Fox formula is shown below and is a relationship between the Tg of a copolymer and the glass transition temperature Tgi of a homopolymer formed by polymerizing the monomers constituting the copolymer separately.

[0186] 1 / Tg=Σ(Wi / Tgi)

[0187] It should be noted that in the above Fox formula, Tg represents the glass transition temperature of the copolymer (unit: K), Wi represents the mass fraction of monomer i in the copolymer (copolymerization ratio based on mass), and Tgi represents the glass transition temperature of the homopolymer of monomer i (unit: K).

[0188] As the glass transition temperature of the homopolymer used for calculation of Tg, the value described in the known document is used. For example, for the monomers listed below, the following values ​​are used as the glass transition temperature of the homopolymer of the monomer.

[0189] 2-Ethylhexyl acrylate -70℃

[0190] Isononyl acrylate-60℃

[0191] n-Butyl acrylate-55℃

[0192] Ethyl acrylate -22℃

[0193] Methyl acrylate 8℃

[0194] Methyl methacrylate 105℃

[0195] 2-Hydroxyethyl acrylate -15℃

[0196] 4-Hydroxybutyl acrylate -40℃

[0197] Vinyl acetate 32℃

[0198] Acrylic acid 106℃

[0199] Methacrylic acid 228℃

[0200] N-vinyl-2-pyrrolidone 54℃

[0201] Regarding the glass transition temperature of the homopolymer of the monomer other than the above-mentioned examples, the numerical value recorded in the "Polymer Handbook" (3rd edition, John Wiley & Sons, Inc., 1989) is used. Regarding the monomers for which multiple values ​​are recorded in this document, the highest value is adopted. In the case where there is no record in the above-mentioned polymer handbook, the value obtained by the determination method recorded in Japanese Patent Publication No. 2007-51271 is used.

[0202] The Tg of a polymer can be adjusted by appropriately changing the monomer composition (that is, the types and amount ratio of the monomers used in the synthesis of the polymer).

[0203] For example, in order to make the storage modulus of the adhesive layer within the desired range, the adhesive composition forming the above-mentioned first adhesive layer 1 can be preferably implemented in the following form: containing 50% by mass or more of a homopolymer with a lower Tg and a straight or branched alkyl group with 4 to 18 carbon atoms (hereinafter, sometimes referred to as "(meth)acrylate C4-18 alkyl ester") as a monomer component constituting the polymer relative to the total amount of the monomer component. The amount of (meth)acrylate C4-18 alkyl ester is more preferably 70% by mass or more, further preferably 85% by mass or more, and particularly preferably 90% by mass or more. On the other hand, from the viewpoint of cohesion, etc., it is generally appropriate that the amount of (meth)acrylate C4-18 alkyl ester is 99.5% by mass or less relative to the total amount of the monomer component, and can also be 98% by mass or less (for example, less than 97% by mass).

[0204] For the same purpose, the adhesive composition forming the first adhesive layer 1 can be preferably implemented in the following form: containing 0.1% by mass or more of a homopolymer with a low Tg as a monomer component constituting the polymer relative to the total amount of the monomer component. The amount of the hydroxyl-containing monomer is preferably 0.5% by mass or more, and more preferably 1% by mass or more relative to the total amount of the monomer component. In addition, the amount of the hydroxyl-containing monomer is preferably 20% by mass or less, and can also be 10% by mass or less (e.g., 5% by mass or less) relative to the total amount of the monomer component.

[0205] In order to make the storage modulus within the desired range, among the polymers contained in the adhesive composition forming the first adhesive layer 1, it is preferred that the homopolymer has a high Tg, and the total content of an alkyl (meth)acrylate having a linear alkyl group having 1 to 3 carbon atoms (hereinafter, sometimes referred to as "C1-3 linear alkyl (meth)acrylate"), an alkyl (meth)acrylate having a branched alkyl group having 3 or 4 carbon atoms (hereinafter, sometimes referred to as "C3-4 branched alkyl (meth)acrylate"), and an alicyclic monomer is 10% by mass or less relative to the total amount of the monomer components.

[0206] The method for obtaining the acrylic polymer is not particularly limited, and various polymerization methods known as methods for synthesizing acrylic polymers such as solution polymerization, emulsion polymerization, bulk polymerization, suspension polymerization, and photopolymerization can be appropriately adopted.

[0207] For example, when solution polymerization is used, the polymerization temperature during solution polymerization can be appropriately selected according to the types of monomers and solvents used, the type of polymerization initiator, etc., and can be, for example, 20°C to 170°C (typically 40°C to 140°C).

[0208] The solvent (polymerization solvent) used in the solution polymerization can be appropriately selected from conventionally known organic solvents. For example, any one solvent selected from aromatic compounds such as toluene (typically aromatic hydrocarbons); acetates such as ethyl acetate; aliphatic or alicyclic hydrocarbons such as hexane or cyclohexane; halogenated alkanes such as 1,2-dichloroethane; lower alcohols such as isopropanol (e.g. monohydric alcohols having 1 to 4 carbon atoms); ethers such as tert-butyl methyl ether; ketones such as methyl ethyl ketone; etc., or a mixed solvent of two or more thereof can be used.

[0209] The initiator used in the polymerization can be appropriately selected from the conventionally known polymerization initiators according to the type of polymerization method. For example, one or more azo polymerization initiators such as 2,2'-azobisisobutyronitrile (AIBN) can be preferably used. Other examples of polymerization initiators include: persulfates such as potassium persulfate; peroxide initiators such as benzoyl peroxide and hydrogen peroxide; substituted ethane initiators such as phenyl-substituted ethane; aromatic carbonyl compounds, etc. As other examples of polymerization initiators, redox initiators based on a combination of peroxides and reducing agents can be listed. Such polymerization initiators can be used alone or in combination of two or more. The amount of the polymerization initiator used can be any amount normally used, for example, it can be selected from the range of 0.005 to 1 part by mass (typically 0.01 to 1 part by mass) relative to 100 parts by mass of the monomer component.

[0210] (Solvent)

[0211] The polymer in the third form is solid, so the solvent-based adhesive composition is a solution of the polymer dissolved in an organic solvent. For example, a polymer solution is obtained by polymerizing a monomer component solution. A polymer solution can also be prepared by dissolving a solid polymer in an organic solvent.

[0212] The solvent may be, for example, a single solvent containing any one of toluene, xylene, ethyl acetate, hexane, cyclohexane, methylcyclohexane, heptane and isopropanol, or a mixed solvent containing any one of these as a main component. The solution concentration is usually about 20% to 80% by mass.

[0213] (Colorant)

[0214] The solvent-based adhesive composition used for forming the adhesive layer of the third embodiment may contain a colorant. In particular, the solvent-based adhesive composition forming the first adhesive layer 1 preferably contains a colorant.

[0215] As long as the colorant can be dissolved or dispersed in the solvent-based adhesive composition, it can be either a dye or a pigment. From the perspective of being able to achieve low haze even when added in small amounts, and being easy to be evenly distributed without sedimentation like a pigment, a dye is preferred. In addition, from the perspective of having high color development even when added in small amounts, a pigment is preferred. When a pigment is used as a colorant, a pigment with low or no conductivity is preferred. In addition, when a dye is used, it is preferably used in combination with an antioxidant, etc.

[0216] The colorant contained in the solvent-based pressure-sensitive adhesive composition in the third embodiment further includes an ultraviolet absorbing colorant in addition to the ultraviolet transmissive colorant described in the first embodiment.

[0217] As ultraviolet-transmitting black pigments, "9050 BLACK" and "UVBK-0001" manufactured by TOKUSHIKI can be cited. As ultraviolet-absorbing black dyes, "VALIFAST BLACK 3810" and "NUBIAN Black PA-2802" manufactured by Orient Chemical Industries can be cited. As ultraviolet-absorbing black pigments, carbon black, titanium black, etc. can be cited. Among them, the colorant preferably contains carbon black.

[0218] The content of the colorant in the solvent-based adhesive composition is, for example, about 0.01 to 20 parts by mass relative to 100 parts by mass of the total monomer amount, and can be appropriately set according to the type of colorant, the color tone and light transmittance of the adhesive layer, etc. The colorant can be added to the composition in the form of a solution or dispersion dissolved or dispersed in an appropriate solvent.

[0219] (Crosslinking agent)

[0220] The solvent-based PSA composition according to the third embodiment may contain a crosslinking agent capable of crosslinking with the polymer.

[0221] When the solvent-based PSA composition contains a crosslinking agent in the third embodiment, the crosslinking agent is preferably an isocyanate crosslinking agent, a peroxide crosslinking agent, or an epoxy crosslinking agent, as described above for the second embodiment.

[0222] In the third aspect, when the solvent-based adhesive composition contains a crosslinking agent, the content thereof can be appropriately adjusted so that the storage modulus of the adhesive layer reaches a desired range. For example, the content thereof is about 0.01 to about 5 parts by mass relative to 100 parts by mass of the polymer, and may be 0.05 parts by mass or more, 0.1 parts by mass or more, or 0.2 parts by mass or more, and may be 3 parts by mass or less, 2 parts by mass or less, or 1 part by mass or less.

[0223] (Other ingredients)

[0224] The solvent-based adhesive composition of the third embodiment may contain, in addition to the above-mentioned components, oligomers, tackifiers, silane coupling agents, crosslinking catalysts, crosslinking inhibitors, chain transfer agents, plasticizers, softeners, anti-degradation agents, fillers, antioxidants, surfactants, antistatic agents, etc.

[0225] [Method for producing adhesive sheet]

[0226] In the embodiment of the present invention, the pressure-sensitive adhesive sheet 10 can be produced by laminating the second pressure-sensitive adhesive layer 2 on the surface 3 b of the substrate 3 , and further laminating the first pressure-sensitive adhesive layer 1 .

[0227] <First Form>

[0228] There is no particular limitation on the method of laminating the second adhesive layer 2 of the first form on the surface 3b of the substrate 3. For example, the photocurable adhesive composition can be coated on a release liner and formed into a sheet, photocured to produce the sheet-like second adhesive layer 2, and then adhered to the surface 3b of the substrate 3.

[0229] There is no particular limitation on the method of further laminating the first adhesive layer 1 in the first form on the second adhesive layer 2 laminated on the substrate 3. For example, the photocurable adhesive composition can be coated on a release liner and formed into a sheet, and then photocured to produce the sheet-like first adhesive layer 1, which can then be adhered to the second adhesive layer laminated on the surface 3b of the substrate 3.

[0230] The photocurable adhesive composition is coated into a sheet (layer) on a release liner, and the film of the adhesive composition on the release liner is irradiated with ultraviolet rays, and photocuring is performed to obtain the first adhesive layer or the second adhesive layer of the first form. When photocuring, it is preferred that a release liner is further additionally provided on the surface of the film, and ultraviolet rays are irradiated under the state that the photocurable adhesive composition is sandwiched between two release liners, thereby preventing the inhibition caused by oxygen. Before photocuring, in order to remove the solvent or dispersion medium of the colorant, the sheet-like film can be heated. In the case of removing the solvent etc. by heating, it is preferably implemented before the release liner is additionally provided.

[0231] As the film substrate of the release liner, a film containing various resin materials is used. As the resin material, polyester resins such as polyethylene terephthalate and polyethylene naphthalate, acetate resins, polyethersulfone resins, polycarbonate resins, polyamide resins, polyimide resins, polyolefin resins, (meth) acrylic resins, polyvinyl chloride resins, polyvinylidene chloride resins, polystyrene resins, polyvinyl alcohol resins, polyarylate resins, polyphenylene sulfide resins, etc. can be listed. Among them, polyester resins such as polyethylene terephthalate are particularly preferred. The thickness of the film substrate is preferably 10μm to 200μm, and more preferably 25μm to 150μm. As the material of the release layer, polysilicone release agents, fluorine-containing release agents, long-chain alkyl release agents, fatty acid amide release agents, etc. can be listed. The thickness of the release layer is generally about 10nm to about 2000nm.

[0232] As a method for coating the adhesive composition on the release liner, various methods such as roll coating, lick roll coating, gravure coating, reverse coating, roll brush, spray coating, dip roll coating, bar coating, knife coating, air knife coating, curtain coating, lip die coating, and die coater can be used.

[0233] By irradiating the photocurable adhesive composition coated in a layer on the release liner with ultraviolet rays, active species are generated from the photopolymerization initiator, and the photopolymerizable compound is polymerized, and the liquid photocurable adhesive composition becomes a solid (fixed) adhesive layer with an increase in the polymerization rate (reduction in unreacted monomers). There is no particular limitation on the light source used for ultraviolet irradiation as long as it can irradiate light in the wavelength range to which the photopolymerization initiator contained in the photocurable adhesive composition has sensitivity, and LED light sources, high-pressure mercury lamps, ultra-high-pressure mercury lamps, metal halide lamps, xenon lamps, etc. can be used.

[0234] The cumulative amount of irradiation light is, for example, about 100 mJ / cm 2 ~About 5000mJ / cm 2 The polymerization rate (non-volatile component) of the adhesive layer of the photocured material containing the photocurable adhesive composition is preferably 80% or more, more preferably 85% or more, and further preferably 90% or more. The polymerization rate may be 93% or more or 95% or more. In order to reduce the non-volatile component, the adhesive layer may be heated to remove volatile components such as residual monomers, unreacted polymerization initiators, and solvents.

[0235] Under the situation that release liner is set on the two sides of adhesive layer, the thickness of a release liner can be identical with the thickness of another release liner, also can be different.The release force when peeling off the release liner temporarily attached to a face from adhesive layer and the release force when peeling off the release liner temporarily attached to another face from adhesive layer can be identical with or can be different.Under the situation that both release forces are different, first the relatively little release liner (light release liner) of release force is peeled off and attached to the face 3b of base material 3 from the second adhesive layer 2, then from the second adhesive layer 2, the relatively big release liner (heavy release liner) of release force is peeled off, the second adhesive layer is exposed.Then, the light release liner is peeled off from the first adhesive layer 1, and is attached to the described second adhesive layer exposed, can make the adhesive sheet of the first adhesive layer and the second adhesive layer with the first form thus.

[0236] In addition, as another method for stacking the second adhesive layer 2 of the first form on the surface 3b of the substrate 3, the following method can also be listed: the above-mentioned photocurable adhesive composition is coated on the surface 3b of the substrate 3, and after being formed into a sheet, a release liner is additionally provided on the surface of the coating film, and ultraviolet rays are irradiated, thereby stacking the second adhesive layer on the substrate 3.

[0237] <Second Form>

[0238] There is no particular limitation on the method of laminating the second adhesive layer 2 of the second form on the surface 3b of the substrate 3. For example, the second adhesive layer can be formed by coating the above-mentioned second form of the photocurable adhesive composition on a release liner, drying and removing the solvent as needed, and adhering it to the surface 3b of the substrate 3.

[0239] In addition, as another method for laminating the second adhesive layer 2 of the second form on the surface 3b of the substrate 3, the following method can be listed: the above-mentioned second form of the photocurable adhesive composition is applied to the surface 3b of the substrate 3, and the solvent is dried to remove it as needed, thereby forming the second adhesive layer.

[0240] There is no particular limitation on the method of further laminating the first adhesive layer 1 of the second form on the second adhesive layer 2 laminated on the substrate 3. For example, the first adhesive layer can be prepared by coating the above-mentioned second form of the photocurable adhesive composition on a release liner, drying and removing the solvent as needed to form a first adhesive layer, and then sticking the above-mentioned second adhesive layer laminated on the surface 3b of the substrate 3.

[0241] When the photocurable adhesive composition contains a solvent, it is preferred to dry the solvent after applying the adhesive composition. As a drying method, an appropriate method can be appropriately adopted according to the purpose. The heating drying temperature is preferably 40°C to 200°C, more preferably 50°C to 180°C, and particularly preferably 70°C to 170°C. The drying time can be appropriately used for an appropriate time. The drying time is preferably 5 seconds to 20 minutes, more preferably 5 seconds to 15 minutes, and particularly preferably 10 seconds to 10 minutes.

[0242] After applying the photocurable adhesive composition, heating is performed as required to introduce a crosslinking structure into the polymer. The heating temperature and heating time can be appropriately set according to the type of crosslinking agent used, and are usually heated in the range of 20°C to 160°C for about 1 minute to about 7 days. The heating for drying the solvent can also be used as the heating for crosslinking. The introduction of the crosslinking structure does not necessarily require heating.

[0243] The first adhesive layer and the second adhesive layer of the second form are not photocured and therefore contain the photopolymerizable compound in an unreacted state. That is, the first adhesive layer and the second adhesive layer of the second form are photocurable adhesive layers containing a polymer, a photopolymerizable compound, a photopolymerization initiator, and a colorant as required.

[0244] The adhesive sheet having the second form of the photocurable first adhesive layer and / or the second adhesive layer can be photocured by irradiating ultraviolet rays after being attached to the display panel described later. The adhesive force between the adhesive sheet and the display panel can be changed by photocuring. For example, the adhesive layer before photocuring has high flexibility, so it can fill the concave and convex shapes and height differences formed by the light-emitting elements arranged on the display panel, and after photocuring, the adhesive force and adhesive reliability to the display panel can be improved.

[0245] Ultraviolet rays are used as active rays for photocuring the adhesive layer. As in the first form of the adhesive layer, when a colorant that transmits ultraviolet rays is used, the transmittance of ultraviolet rays is greater than that of visible light, so even when the thickness of the adhesive layer is large, curing hindrance during photocuring can be suppressed.

[0246] <Third Form>

[0247] There is no particular limitation on the method for laminating the third-form second adhesive layer 2 on the surface 3b of the substrate 3. For example, the method can be carried out by coating the third-form solvent-based adhesive composition on a release liner, drying and removing the solvent as needed to form a second adhesive layer, and pasting it on the surface 3b of the substrate 3.

[0248] In addition, as another method for laminating the third form of the second adhesive layer 2 on the surface 3b of the substrate 3, the following method can be cited: the above-mentioned third form of the solvent-based adhesive composition is applied to the surface 3b of the substrate 3, and the solvent is dried to remove it as needed, thereby forming the second adhesive layer.

[0249] There is no particular limitation on the method of further laminating the third-form first adhesive layer 1 on the second adhesive layer 2 laminated on the substrate 3. For example, the third-form solvent-based adhesive composition can be coated on a release liner, and the first adhesive layer can be formed by drying and removing the solvent as needed, and then affixing the first adhesive layer to the second adhesive layer laminated on the surface 3b of the substrate 3.

[0250] After applying the solvent-based adhesive composition, the solvent is dried. As a drying method, an appropriate method can be appropriately adopted according to the purpose. The heating drying temperature is preferably 40°C to 200°C, more preferably 50°C to 180°C, and particularly preferably 70°C to 170°C. The drying time can be appropriately adopted for an appropriate time. The drying time is preferably 5 seconds to 20 minutes, more preferably 5 seconds to 15 minutes, and particularly preferably 10 seconds to 10 minutes.

[0251] After the solvent-based adhesive composition is applied, it may be heated as needed. The heating temperature and heating time may be appropriately set according to the type of crosslinking agent used, and are usually heated within the range of 20° C. to 160° C. for about 1 minute to about 7 days.

[0252] In the adhesive sheet of the embodiment of the present invention, a release liner may be provided on the first adhesive layer until use. In addition, in the adhesive sheet of the embodiment of the present invention, a surface protective film may be laminated on the surface 3a of the substrate 3. The surface protective film is suitable for preventing damage and dirt from being attached during the manufacture, transportation, and shipment of the above-mentioned adhesive sheet and the optical product including the adhesive sheet.

[0253] In the adhesive sheet of the embodiment of the present invention, in addition to the first adhesive layer 1, the second adhesive layer 2, the substrate 3, the release liner, and the surface protective film, other layers may be included on the surface or between any layers, such as a substrate other than the substrate 3, an adhesive layer other than the first adhesive layer 1 and the second adhesive layer 2, an intermediate layer, a primer layer, etc., within the range that does not impair the effects of the present invention.

[0254] (Black Matrix)

[0255] The pressure-sensitive adhesive sheet according to the embodiment of the present invention can be used as a black matrix sheet. When the pressure-sensitive adhesive sheet according to the embodiment of the present invention is used as a black matrix sheet, it is preferred that the first pressure-sensitive adhesive layer contains a colorant.

[0256] For example, in the case of encapsulating a substrate having fine chip components such as self-luminous bodies, by arranging and pressing the substrate having the chip components and the adhesive sheet of the embodiment of the present invention such that the surface on the side of the first adhesive layer of the adhesive sheet faces the chip component side, it is possible to simultaneously perform the encapsulation of the substrate having the chip components and the formation of the black matrix layer.

[0257] As described above, the first adhesive layer 1 can encapsulate between the respective LED chips 7 and the metal wiring layer 6 in the display panel in which the LED chips and the metal wiring layer are arranged on the substrate. The visible light transmittance of the first adhesive layer 1 is less than the visible light transmittance of the second adhesive layer 2, and thus it has sufficient light-shielding properties in the visible light region. When the first adhesive layer 1 contains a colorant, the first adhesive layer 1 with higher light-shielding properties encapsulates between the respective LED chips 7 without gaps, enabling the formation of the black matrix layer, preventing color mixing between the respective LED chips 7, and improving the contrast. In addition, the first adhesive layer 1 with higher light-shielding properties also encapsulates the surface of the metal wiring layer 6, and thus it is possible to prevent reflection caused by the metal wiring layer 6.

[0258] [Laminated body]

[0259] The laminated body of the embodiment of the present invention is a laminated body in which a chip component and the adhesive sheet of the embodiment of the present invention are laminated on a substrate.

[0260] As the chip component, for example, the following can be cited: optical components such as self-luminous bodies, light-emitting elements, and semiconductor chips. As the light-emitting element, for example, LED chips, small / micro LED chips, etc. can be cited.

[0261] The laminated body of another embodiment of the present invention is a laminated body in which a display panel having a light-emitting element on a substrate, a first adhesive layer, a second adhesive layer, and a base material are laminated in sequence, wherein the visible light transmittance T1 of the first adhesive layer and the visible light transmittance T2 of the second adhesive layer satisfy T1 < T2, and the thickness of the first adhesive layer in the portion of the substrate that does not have the light-emitting element is 2.5 times or more the thickness of the first adhesive layer in the portion that has the light-emitting element.

[0262] The laminated body of the embodiment of the present invention can be appropriately manufactured using the adhesive sheet of the embodiment of the present invention.

[0263] For example, in the case of encapsulating a substrate having fine chip components such as light-emitting elements, by arranging and pressing the substrate having the chip components and the adhesive sheet of the embodiment of the present invention such that the surface on the side of the first adhesive layer of the adhesive sheet faces the chip component, it is possible to encapsulate the substrate having the chip components.

[0264] The laminated body according to the embodiment of the present invention may be an optical laminated body.

[0265] It should be noted that the "optical" in the optical laminate of the embodiment of the present invention refers to a laminate for optical purposes, and more specifically, refers to a laminate for manufacturing products (optical products) using optical components. As optical products, for example, image display devices, input devices such as touch panels, etc. can be listed, preferably small / micro LED display devices, organic EL (electroluminescent) display devices and other optical laminates, especially can be appropriately used in the manufacture of micro LED display devices.

[0266] The stacked body of an embodiment of the present invention can be a display device as follows: a plurality of tiny light-emitting elements are arranged on a wiring substrate, and each light-emitting element is selectively illuminated by a light-emitting control unit connected thereto, so that visual information such as text, images, and dynamic images can be directly displayed on a display screen by flashing each light-emitting element.

[0267] Examples of the laminate include small / micro LED display devices and organic EL (electroluminescence) display devices.

[0268] The display panel in the laminated body according to the embodiment of the present invention is preferably an LED panel having micro LED chips on a substrate, and may be an LED panel having a plurality of micro LED chips arranged on at least one surface of a substrate.

[0269] The pressure-sensitive adhesive sheet according to the embodiment of the present invention is suitable for use in the production of a laminate, and is particularly suitable for use in the production of a micro LED display device.

[0270] The present invention also relates to a method for producing a laminate using the pressure-sensitive adhesive sheet.

[0271] Figure 2 An example of a schematic diagram (cross-sectional view) of a laminate (micro LED display device) according to an embodiment of the present invention. In the micro LED display device 20 according to an embodiment of the present invention, a display panel having a plurality of LEDs 7 arranged on a single surface of a substrate 5, a first adhesive layer 1, a second adhesive layer 2, and a base material 3 are stacked in sequence.

[0272] In the micro-LED display device of the embodiment of the present invention, the first adhesive layer 1 can encapsulate the LED chips 7 and the metal wiring layer 6 on the substrate. The visible light transmittance of the first adhesive layer 1 is lower than the visible light transmittance of the second adhesive layer 2, so that it has sufficient light shielding properties in the visible light region. Since the first adhesive layer 1 with higher light shielding properties (low transmittance) encapsulates the LED chips 7 without gaps, it is possible to prevent color mixing between the LED chips 7 and improve the contrast. In addition, the first adhesive layer 1 with higher light shielding properties (low transmittance) also encapsulates the surface of the metal wiring layer 6, so it is possible to prevent reflection caused by the metal wiring layer 6.

[0273] In the embodiment of the present invention, the second adhesive layer 2 encapsulates the upper part (image display side) of each LED chip 7 on the substrate. The visible light transmittance of the second adhesive layer 2 is higher than that of the first adhesive layer 1, and has sufficient transmittance in the visible light region. The second adhesive layer 2 with higher light transmittance encapsulates the upper part (image display side) of each LED chip 7, so the absorption of visible light emitted from each LED chip 7 is suppressed to a lower level, which can improve the luminous efficiency, thereby making the image brighter. In addition, since there is no need to increase the output power to increase the luminous brightness, the power consumption can be suppressed to a lower level.

[0274] As described above, the thickness of the second adhesive layer 2 of the adhesive sheet of the embodiment of the present invention is less than 100 μm, and the storage modulus G1' of the first adhesive layer 1 at 90°C is less than the storage modulus G2' of the second adhesive layer 2 at 90°C. Therefore, in the laminate obtained by encapsulating the light-emitting elements (micro-LED light-emitting elements) arranged on the LED panel having micro-LED chips on the substrate, the first adhesive layer with a lower visible light transmittance is not likely to remain on the upper part (image display side) of the light-emitting element. Therefore, the luminous efficiency of the light-emitting element can be improved.

[0275] In the laminated body 20 of the embodiment of the present invention, the thickness of the first adhesive layer 1 in the portion of the substrate 5 where the light emitting element 7 is not arranged ( Figure 2 The x shown in FIG. 1 (hereinafter referred to as thickness (x)) is the thickness ( Figure 2 The thickness (y) shown in FIG. 1 is set to be at least 2.5 times the thickness (y) below. From the viewpoint of improving the luminous efficiency of the light-emitting element, the thickness (y) is preferably thinner, and the thickness (x) is preferably at least 3.0 times the thickness (y), and more preferably at least 3.5 times.

[0276] The laminate of the embodiment of the present invention may have optical components other than the display panel and the adhesive sheet. As the above-mentioned optical components, there are no particular restrictions, and examples include: polarizing plates, phase difference plates, anti-reflection films, viewing angle adjustment films, optical compensation films, etc. It should be noted that the optical components also include components (design films, decorative films, surface protection plates, etc.) that play a decorative and protective role while maintaining the visual recognition of display devices and input devices.

[0277] The micro LED display device according to the embodiment of the present invention can be manufactured by bonding a display panel having an LED chip on a substrate and the first adhesive layer of the adhesive sheet according to the embodiment of the present invention.

[0278] Specifically, the display panel and the pressure-sensitive adhesive sheet having the first pressure-sensitive adhesive layer and / or the second pressure-sensitive adhesive layer of the first form can be attached by laminating them under heating and / or pressure.

[0279] When the display panel and the adhesive sheet having the first adhesive layer and / or the second adhesive layer of the second form are attached, the adhesive sheet can be laminated under heating and / or pressure and then photocured. The photocuring can be performed in the same manner as the photocuring of the first adhesive layer and / or the second adhesive layer of the first form.

[0280] The display panel and the pressure-sensitive adhesive sheet having the first pressure-sensitive adhesive layer and / or the second pressure-sensitive adhesive layer of the third embodiment can be attached by laminating them under heating and / or pressure.

[0281] The above-mentioned bonding is preferably performed by heating and pressurizing at a temperature above 50°C. By performing heating and pressurizing at a temperature above 50°C, the adhesive layer becomes highly fluid and can fully follow the height difference of the LED chips arranged on the substrate, thereby adhering without gaps. The heating is performed at a temperature above 50°C, preferably above 60°C, and more preferably above 70°C. There is no particular restriction on pressurization, for example, it is performed at a temperature above 1.5atm, preferably above 2atm, and more preferably above 3atm. Heating and pressurizing can be performed, for example, using an autoclave. After the micro LED display device manufactured in this way is restored to room temperature (25°C), the storage modulus of the adhesive layer becomes higher, and the processability and adhesion reliability are improved.

[0282] As described above, the following matters are disclosed in this specification. [1]

[0284] An adhesive sheet, wherein the adhesive sheet has a laminated structure in which a first adhesive layer, a second adhesive layer, and a substrate are laminated in sequence, the visible light transmittance T1 of the first adhesive layer and the visible light transmittance T2 of the second adhesive layer satisfy T1 < T2, the thickness of the second adhesive layer is less than 100 μm, and the storage modulus G1' of the first adhesive layer at 90 °C and the storage modulus G2' of the second adhesive layer at 90 °C satisfy G1' < G2'. [2]

[0286] The adhesive sheet according to [1], wherein G1' and G2' satisfy G1' / G2' < 0.3. [3]

[0288] The adhesive sheet according to [1] or [2], wherein at least one of the first adhesive layer and the second adhesive layer is an adhesive layer formed of an adhesive composition selected from a photocurable adhesive composition and a solvent-based adhesive composition. [4]

[0290] The adhesive sheet according to any one of [1] to [3], wherein the first adhesive layer contains a colorant. [5]

[0292] The adhesive sheet according to [4], wherein the colorant contains carbon black. [6]

[0294] The adhesive sheet according to any one of [1] to [5], wherein the thickness of the first adhesive layer is 5 μm to 10 μm. [7]

[0296] The adhesive sheet according to any one of [1] to [6], wherein the thickness of the second adhesive layer is 10 μm to 99 μm. [8]

[0298] A laminate, wherein a substrate having a chip component and the adhesive sheet according to any one of [1] to [7] are laminated. [9]

[0300] A laminate, which is a laminate in which a display panel having a light-emitting element on a substrate, a first adhesive layer, a second adhesive layer, and a substrate are laminated in sequence, wherein the visible light transmittance T1 of the first adhesive layer and the visible light transmittance T2 of the second adhesive layer satisfy T1 < T2, and the thickness of the first adhesive layer in a portion of the substrate that does not have the light-emitting element is 2.5 times or more the thickness of the first adhesive layer in a portion of the substrate that has the light-emitting element.

[10]

[0302] The stacked body according to [9], wherein the display panel is an LED panel having a micro LED chip on a substrate.

[0303] Example

[0304] Hereinafter, the present invention will be specifically described by way of examples, but the present invention is not limited to these examples.

[0305] <Visible light transmittance>

[0306] Using the PSA sheets prepared in Examples and Comparative Examples, the visible light transmittances T1 and T2 of the first PSA layer and the second PSA layer were measured by the following operation.

[0307] The release liner on one side of the adhesive sheet was peeled off, and an alkali-free glass was attached to the exposed side. Then, the release liner on the other side of the adhesive sheet was peeled off, and the adhesive sheet was attached to an alkali-free glass plate, thereby obtaining a sample. Using this sample, the transmittance of the evaluation sample was measured according to JIS K7361-1 using a visible ultraviolet spectrophotometer (manufactured by Murakami Color Research Laboratory, trade name "HSP-150Vis").

[0308] <Storage modulus>

[0309] The storage moduli G1' and G2' of the first and second adhesive layers were measured by the following operation using the adhesive sheets prepared in Examples and Comparative Examples.

[0310] The adhesive layer from which the release liner was peeled off was stacked and stacked to a thickness of about 1 mm, and the resulting laminate was used as a measurement sample. The above-mentioned laminate was cut into a diameter of 8 mm to prepare a test piece. Using a fixture with a diameter of 8 mm, a temperature dispersion of -50°C to 150°C was performed using a viscoelastic device ARES-G2 manufactured by TA Instruments. At this time, the heating rate was 5°C / min, the frequency was 1Hz, and the strain was 0.1%. At this time, the elastic modulus at 90°C was used as the storage modulus (kPa) of the adhesive layer.

[0311] <Film thickness>

[0312] The film thickness of the adhesive layer was measured using a micrometer (GC-9 manufactured by Peacock). The thickness of the adhesive sheet prepared in the Examples and Comparative Examples was measured, and the thickness (μm) of the release liner of the adhesive layer at that location was measured, and the difference was taken as the thickness (μm) of the adhesive layer. The average thickness (μm) was the average value of 10 points.

[0313] [Preparation of Colored Adhesive Composition for Forming First Adhesive Layer]

[0314] <Preparation of Adhesive Composition A>

[0315] In a reaction vessel equipped with a stirrer, a thermometer, a reflux condenser, and a nitrogen inlet tube, a mixture containing 96 parts by mass of 2-ethylhexyl acrylate, 4 parts by mass of 2-hydroxyethyl acrylate, 0.2 parts by mass of 2,2'-azobisisobutyronitrile (AIBN) as a polymerization initiator, and 200 parts by mass of ethyl acetate as a solvent was stirred at 60°C under a nitrogen atmosphere for 7 hours (polymerization reaction). Thus, a polymer solution containing an acrylic polymer was obtained. The weight average molecular weight (Mw) of the acrylic polymer in the polymer solution was 600,000.

[0316] <Preparation of Adhesive Composition B>

[0317] In a reaction vessel equipped with a stirrer, a thermometer, a reflux condenser, and a nitrogen inlet tube, a mixture containing 99 parts by mass of butyl acrylate, 1 part by mass of 4-hydroxybutyl acrylate, 0.2 parts by mass of 2,2'-azobisisobutyronitrile (AIBN) as a polymerization initiator, and 500 parts by mass of ethyl acetate as a solvent was stirred at 60°C under a nitrogen atmosphere for 7 hours (polymerization reaction). Thus, a polymer solution containing an acrylic polymer was obtained. The weight average molecular weight (Mw) of the acrylic polymer in the polymer solution was 600,000.

[0318] <Preparation of Colored Adhesive Composition 1>

[0319] To the polymer solution containing the acrylic polymer of the above-mentioned adhesive composition A, 0.1 parts by mass (solid content conversion amount) of an isocyanate crosslinking agent (trade name "CORONATE HX", manufactured by Tosoh Corporation) as a crosslinking agent and 3 parts by mass of acetylacetone as a crosslinking inhibitor (ligand for the crosslinking catalyst) were added relative to 100 parts by mass of the acrylic polymer, and a black pigment dispersion (trade name "ATDN101 BLACK", manufactured by Dainichi Seika Industries) was added so that the pigment concentration became 3.2% by mass, and mixed to obtain a colored adhesive composition 1.

[0320] <Preparation of Colored Adhesive Composition 2>

[0321] To the polymer solution containing the acrylic polymer of the above-mentioned adhesive composition A, 0.4 parts by mass (solid content conversion amount) of an isocyanate crosslinking agent (trade name "CORONATE HX", manufactured by Tosoh Corporation) as a crosslinking agent, 0.01 parts by mass (solid content conversion amount) of iron triacetylacetonate (manufactured by Nippon Chemical Industry Co., Ltd.) as a crosslinking catalyst, and 3 parts by mass of acetylacetone as a crosslinking inhibitor (ligand for the crosslinking catalyst) were added, and a black pigment dispersion (trade name "ATDN101 BLACK", manufactured by Dainichi Seika Industries Co., Ltd.) was added so that the pigment concentration became 3.2% by mass, and mixed to obtain a colored adhesive composition 2.

[0322] <Preparation of Colored Adhesive Composition 3>

[0323] To the polymer solution containing the acrylic polymer of the above-mentioned adhesive composition B, 1 part by mass (solid content conversion amount) of a peroxide-based crosslinking agent (trade name "NYPER BMT40SV", manufactured by NOF Corporation) was added as a crosslinking agent relative to 100 parts by mass of the acrylic polymer, and a black pigment dispersion (trade name "ATDN101 BLACK", manufactured by Dainichi Seika Industries) was added so that the pigment concentration became 3.2% by mass, and mixed, thereby obtaining a colored adhesive composition 3.

[0324]

[0325] [Preparation of Adhesive Composition for Forming Second Adhesive Layer]

[0326] <Preparation of Prepolymer 1>

[0327] In a separable flask equipped with a thermometer, a stirrer, a reflux condenser, and a nitrogen inlet tube, 75 parts by mass of 2-ethylhexyl acrylate, 15 parts by mass of N-vinyl-2-pyrrolidone, 10 parts by mass of 2-hydroxyethyl acrylate, 0.04 parts by mass of a photopolymerization initiator (manufactured by BASF, trade name "Irgacure 184"), and 0.04 parts by mass of a photopolymerization initiator (manufactured by BASF, trade name "Irgacure 651") were added, and then nitrogen was circulated and nitrogen replacement was performed for about 1 hour while stirring. Then, the mixture was heated at 5 mW / cm 2 The polymerization was carried out by irradiation with UVA, and the reaction rate was adjusted to be 5% to 15%, thereby obtaining an acrylic prepolymer 1 solution.

[0328] <Preparation of Prepolymer 2>

[0329] In a separable flask equipped with a thermometer, a stirrer, a reflux condenser, and a nitrogen inlet tube, 70 parts by mass of butyl acrylate, 10 parts by mass of cyclohexyl acrylate, 20 parts by mass of 4-hydroxybutyl acrylate, 0.04 parts by mass of a photopolymerization initiator (manufactured by BASF, trade name "Irgacure 184"), and 0.04 parts by mass of a photopolymerization initiator (manufactured by BASF, trade name "Irgacure 651") were added, and then nitrogen was circulated, and nitrogen replacement was performed for about 1 hour while stirring. Then, at 5 mW / cm 2 The polymerization was carried out by irradiation with UVA, and the reaction rate was adjusted to be 5% to 15%, thereby obtaining an acrylic prepolymer 2 solution.

[0330] <Preparation of Prepolymer 3>

[0331] In a separable flask equipped with a thermometer, a stirrer, a reflux condenser, and a nitrogen inlet tube, 40 parts by mass of lauryl acrylate, 40 parts by mass of 2-ethylhexyl acrylate, 10 parts by mass of N-vinyl-2-pyrrolidone, 10 parts by mass of 4-hydroxybutyl acrylate, 0.04 parts by mass of a photopolymerization initiator (manufactured by BASF, trade name "Irgacure 184"), and 0.04 parts by mass of a photopolymerization initiator (manufactured by BASF, trade name "Irgacure 651") were placed, and then nitrogen was circulated, and nitrogen replacement was performed for about 1 hour while stirring. Then, the temperature was 5 mW / cm 2 The polymerization was carried out by irradiation with UVA, and the reaction rate was adjusted to be 5 to 15%, thereby obtaining an acrylic prepolymer 3 solution.

[0332] <Preparation of Adhesive Composition 1>

[0333] To the acrylic prepolymer 1 solution obtained above (the total amount of the prepolymer was 100 parts by mass), 20 parts by mass of 2-hydroxyethyl acrylate, 4 parts by mass of 1,6-hexanediol diacrylate as a multifunctional monomer, and 0.4 parts by mass of 3-glycidoxypropyltrimethoxysilane as a silane coupling agent were added to prepare a photopolymerizable adhesive composition 1 solution.

[0334] <Preparation of Adhesive Composition 2>

[0335] A photopolymerizable adhesive composition 2 solution was prepared in the same manner as the adhesive composition 1 except that the added amount of 1,6-hexanediol diacrylate was changed to 6 parts by mass.

[0336] <Preparation of Adhesive Composition 3>

[0337] To the acrylic prepolymer 2 solution obtained above (the total amount of the prepolymer was 100 parts by mass), 10 parts by mass of 2-hydroxyethyl acrylate, 10 parts by mass of 4-hydroxybutyl acrylate, 2 parts by mass of dipentaerythritol hexaacrylate as a multifunctional monomer, and 0.4 parts by mass of 3-glycidoxypropyltrimethoxysilane as a silane coupling agent were added to prepare a photopolymerizable adhesive composition 3 solution.

[0338] <Preparation of Adhesive Composition 5>

[0339] A photopolymerizable adhesive composition 5 solution was prepared in the same manner as the adhesive composition 1 except that the added amount of 1,6-hexanediol diacrylate was changed to 0.1 parts by mass.

[0340] <Preparation of Adhesive Composition 6>

[0341] A photopolymerizable adhesive composition 6 solution was prepared in the same manner as the adhesive composition 1 except that the added amount of 1,6-hexanediol diacrylate was changed to 0.3 parts by mass.

[0342] <Preparation of Adhesive Composition 7>

[0343] 0.1 parts by mass of 1,6-hexanediol diacrylate as a polyfunctional monomer and 0.4 parts by mass of 3-glycidoxypropyltrimethoxysilane as a silane coupling agent were added to the acrylic prepolymer 3 solution obtained above (the total amount of the prepolymer was 100 parts by mass) to prepare a photopolymerizable adhesive composition 7 solution.

[0344]

[0345] <Preparation of Adhesive Composition 4>

[0346] (Preparation of Adhesive Composition C)

[0347] In a reaction vessel equipped with a stirrer, a thermometer, a reflux condenser and a nitrogen inlet tube, a mixture containing 60 parts by mass of 2-ethylhexyl acrylate, 20 parts by mass of N-vinyl-2-pyrrolidone, 10 parts by mass of methyl methacrylate, 10 parts by mass of 2-hydroxyethyl acrylate, 0.2 parts by mass of 2,2'-azobisisobutyronitrile (AIBN) as a polymerization initiator, and 200 parts by mass of ethyl acetate as a solvent was stirred at 60°C under a nitrogen atmosphere for 7 hours (polymerization reaction). Thus, a polymer solution containing an acrylic polymer was obtained. The weight average molecular weight (Mw) of the acrylic polymer in the polymer solution was 1.2 million.

[0348] (Preparation of Adhesive Composition 4)

[0349] To the polymer solution containing the acrylic polymer of the above-mentioned adhesive composition C, 2.5 parts by mass (solid content conversion amount) of an isocyanate crosslinking agent (trade name "TAKENATE D110N", manufactured by Mitsui Chemicals) as a crosslinking agent, 0.02 parts by mass (solid content conversion amount) of dibutyltin dilaurate (trade name "OL-1", 1% by mass ethyl acetate solution (manufactured by Tokyo Fine Chemicals Co., Ltd.) as a crosslinking catalyst, and 3 parts by mass of acetylacetone as a crosslinking inhibitor (ligand for the crosslinking catalyst) were added and mixed with each other, thereby obtaining an adhesive composition 4.

[0350]

[0351] [Example 1]

[0352] <Preparation of First Adhesive Sheet>

[0353] The above-mentioned colored adhesive composition 1 is applied to the peeling treatment surface of a polyester film A (trade name "DIAFOIL MRF", manufactured by Mitsubishi Chemical Corporation) with a thickness of 38 μm and a peeling treatment with polysiloxane on one side to form a coating film. Then, the coating film is dried at 130°C for 3 minutes to form an adhesive layer with a thickness of 8 μm. The peeling treatment surface of a polyester film B (trade name "DIAFOIL MRF", manufactured by Mitsubishi Chemical Corporation) with a thickness of 38 μm and a peeling treatment with polysiloxane on one side is attached to the adhesive layer. Then, the first adhesive sheet 1 is obtained by aging at 50°C for 5 days and performing a cross-linking reaction in the adhesive layer.

[0354] <Preparation of Second Adhesive Sheet>

[0355] The prepared adhesive composition 1 solution was applied to the release surface of a release liner R1 (MRF#38, manufactured by Mitsubishi Resins Co., Ltd.) with a thickness of 38 μm, which became the release surface on one side of the polyester film, so that the thickness after curing became 25 μm, and the release liner R2 (MRE#38, manufactured by Mitsubishi Resins Co., Ltd.) with a thickness of 38 μm, which became the release surface on one side of the polyester film, was covered to block the air. A black light lamp (FL15BL, manufactured by Toshiba Corporation) was used from one side of the laminate at an illumination of 5 mW / cm 2 、Accumulated light quantity 1300mJ / cm 2The ultraviolet rays were irradiated under the conditions of . Thus, a cured product of the above-mentioned adhesive composition, i.e., a second adhesive sheet 1 having an adhesive layer with a thickness of 25 μm sandwiched between the above-mentioned release liners R1 and R2, was obtained in the form of a substrate-free adhesive sheet. It should be noted that the value of the illumination of the above-mentioned black light lamp is based on the measured value of an industrial UV detector (manufactured by TOPCON, trade name: UVR-T1, light receiving part model UD-T36) with a peak sensitivity wavelength of about 350 nm.

[0356] <Preparation of Adhesive Sheet>

[0357] One release liner was peeled off from the second PSA sheet 1 cut into 50 mm×50 mm, and the exposed PSA surface was attached to a 50 mm×50 mm substrate (polyethylene terephthalate sheet, manufactured by Toray Industries, trade name Lumirror U34), and then the other release liner was peeled off to expose the PSA surface.

[0358] The adhesive surface of the first adhesive sheet 1 cut into 50 mm×50 mm was bonded to the adhesive surface of the second adhesive sheet 1 to obtain an adhesive sheet 1 comprising substrate / second adhesive sheet 1 / first adhesive sheet 1 / release liner.

[0359] [Examples 2 to 8, Examples 10 to 13, Comparative Examples 1, 2, and 3]

[0360] PSA sheets 2 to 8, PSA sheets 10 to 13, and comparative PSA sheets 1, 2, and 3 were obtained in the same manner as in Example 1, except that the colored PSA composition used in preparing the first PSA sheet was changed to the colored PSA composition shown in Tables 4 and 5, and the type of the PSA composition used in preparing the second PSA sheet and the thickness of the PSA layer were changed as shown in Tables 4 and 5.

[0361] [Example 9]

[0362] <Preparation of First Adhesive Sheet>

[0363] A first adhesive sheet 9 was prepared in the same manner as in the first adhesive sheet 1 except that the colored adhesive composition 1 was changed to the colored adhesive composition 2 .

[0364] <Preparation of Second Adhesive Sheet>

[0365] A second adhesive sheet 9 was prepared in the same manner as the first adhesive sheet 1 except that the colored adhesive composition 1 was changed to the adhesive composition 4 and an adhesive layer having a thickness of 25 μm was formed.

[0366] <Preparation of Adhesive Sheet>

[0367] A PSA sheet 9 was obtained in the same manner as the PSA sheet 1 except that the first PSA sheet 9 and the second PSA sheet 9 were used instead of the first PSA sheet 1 and the second PSA sheet 1 .

[0368] <Evaluation>

[0369] The following evaluations were performed using the pressure-sensitive adhesive sheets obtained in the above Examples and Comparative Examples. The evaluation methods are as follows.

[0370] (1) Thickness of the first adhesive layer on the chip

[0371] (Preparation of Evaluation Samples)

[0372] An 8-inch wafer subjected to convex processing (shaped to form convex portions) (convex portion dimensions: 20 μm in length×40 μm in width×10 μm in height, convex portion interval: 20 μm in both the vertical and horizontal directions) was prepared as a mock panel.

[0373] The release liner was peeled off from the adhesive sheets obtained in Examples and Comparative Examples, and the exposed adhesive surface was adhered to the surface of the simulated panel having the protrusions, and then treated in an autoclave to obtain evaluation samples comprising substrate / second adhesive layer / first adhesive layer / simulated panel.

[0374] The lamination was performed by pressure difference lamination using the device "MSV300" manufactured by Nitto Seiki Co., Ltd. The conditions for pressure difference lamination were set as vacuum degree: 20 Pa, lamination pressure: 0.1 MPa, and simulated panel (wafer) surface temperature: 90°C. The autoclave conditions were set as pressure: 0.5 MPa, temperature: 90°C, and time: 90 seconds.

[0375] (Thickness measurement)

[0376] The cross section of the evaluation sample prepared above was cut and observed by SEM. The thickness of the first adhesive layer on the convex portion of the pseudo panel was measured based on the obtained SEM image, and the arithmetic average of the three points was taken as the thickness on the chip.

[0377] (2) Compression rate

[0378] The compression rate of the first adhesive layer is calculated by the following formula using the thickness value on the chip obtained in (1) above. If the compression rate obtained is 51% or more, it can be said that the first adhesive layer with low visible light transmittance is unlikely to remain on the chip, and the light emitted by the light-emitting element can be easily extracted.

[0379] Compression rate (%) = {(thickness of the first adhesive layer in the adhesive sheet - thickness of the first adhesive layer on the chip) / thickness of the first adhesive layer in the adhesive sheet} × 100

[0380] (3) Anti-reflectivity

[0381] The sample for evaluation prepared above was irradiated with light from the substrate side using a spectrophotometer (“CM-2600d” manufactured by Konica Minolta), and the brightness of the reflected light (L in the Lab color space) was measured under the following conditions using the SCI method. * If L * When the value is 40 or less, it can be said that the function of preventing reflection of the metal wiring in the laminate is excellent.

[0382] (Measurement conditions)

[0383] Type of light receiving optical system: SCI (including regular reflected light)

[0384] Measurement wavelength range: 360nm-740nm

[0385] Light source: D65

[0386] Measuring diameter MAV: φ8mm

[0387] (4) Ratio of the thickness of the first adhesive layer in the chip placement portion and the non-chip placement portion

[0388] The cross section of the evaluation sample prepared above was cut and observed by SEM. Based on the obtained SEM image, the thickness of the first adhesive layer in the portion of the simulated panel where the convex portion was not configured was measured, and the arithmetic mean of the three points was taken as the thickness of the first adhesive layer in the chip non-configuration portion.

[0389] Based on the obtained first adhesive layer thickness in the non-chip arrangement portion and the first adhesive layer thickness on the chip obtained in (1), their ratio (first adhesive layer thickness in the non-chip arrangement portion / first adhesive layer thickness on the chip) was calculated.

[0390]

[0391]

[0392] It can be seen that when the adhesive sheet of the embodiment is used, the compression rate of the first adhesive layer is high, and the first adhesive layer is not likely to remain on the light-emitting element during the encapsulation of the light-emitting element, so it is easier to extract the light emitted by the light-emitting element. In addition, it can be seen that the anti-reflection function is also excellent.

[0393] The present invention is not limited to the above-described embodiments, but can be variously modified within the scope of the claims. Embodiments obtained by appropriately combining technical means disclosed in different embodiments are also included in the technical scope of the present invention.

[0394] Industrial Applicability

[0395] According to the present invention, it is possible to provide a pressure-sensitive adhesive sheet having a high light extraction function and an excellent antireflection function, and a laminate using the pressure-sensitive adhesive sheet.

[0396] While the present invention has been described in detail and with reference to specific embodiments thereof, it will be apparent to one skilled in the art that various changes and modifications can be made therein without departing from the spirit and scope of the present invention.

[0397] This application is based on the Japanese patent application (Japanese Patent Application No. 2022-158797) filed on September 30, 2022, the contents of which are incorporated herein by reference.

[0398] Description of symbols

[0399] 10 adhesive sheets

[0400] 1First adhesive layer

[0401] 2 Second adhesive layer

[0402] 3. Substrate

[0403] 20-layer stack (micro LED display device)

[0404] 5 substrates

[0405] 6 Metal wiring layers

[0406] 7. Light-emitting element (LED chip)

Claims

1. An adhesive sheet, wherein: The adhesive sheet has a laminated structure in which a first adhesive layer, a second adhesive layer, and a substrate are laminated in this order. The visible light transmittance T1 of the first adhesive layer and the visible light transmittance T2 of the second adhesive layer satisfy T1 <T2, The thickness of the second adhesive layer is less than 100 μm, The storage modulus G1′ of the first adhesive layer at 90° C. and the storage modulus G2′ of the second adhesive layer at 90° C. satisfy G1′ <G2’。 2. The adhesive sheet according to claim 1, wherein The G1' and G2' satisfy G1' / G2'<0.

3.

3. The adhesive sheet according to claim 1, wherein At least one of the first adhesive layer and the second adhesive layer is an adhesive layer formed of an adhesive composition selected from a photocurable adhesive composition and a solvent-based adhesive composition.

4. The adhesive sheet according to claim 1, wherein The first adhesive layer contains a colorant.

5. The adhesive sheet according to claim 4, wherein The colorant contains carbon black.

6. The adhesive sheet according to claim 1, wherein The thickness of the first adhesive layer is 5 μm to 10 μm.

7. The adhesive sheet according to claim 1, wherein The second adhesive layer has a thickness of 10 μm to 99 μm.

8. A laminate, wherein: A substrate having chip components and the adhesive sheet according to any one of claims 1 to 7 are laminated.

9. A laminated body, wherein a display panel having a light-emitting element on a substrate, a first adhesive layer, a second adhesive layer, and a base material are laminated in this order, wherein: The visible light transmittance T1 of the first adhesive layer and the visible light transmittance T2 of the second adhesive layer satisfy T1 <T2, The thickness of the first adhesive layer in a portion of the substrate that does not have the light emitting element is 2.5 times or more the thickness of the first adhesive layer in a portion that has the light emitting element.

10. The laminate according to claim 9, wherein The display panel is an LED panel having micro LED chips on a substrate.

Citation Information

Patent Citations

  • Adhesive composition, pressure sensitive adhesive double coated tape, adhesion method and portable electronic device

    JP2007051271A

  • Antiglare hard coat film, manufacturing method of same, optical element, polarizing plate, and image display apparatus

    JP2008090263A

  • Light absorption layer contained in color filter for organic electroluminescence display and sheet using the same

    JP2017203810A

  • display device

    JP2018523854A

  • Self-luminous display

    JP2019204905A